Discovering hidden candidate plastic-degrading enzymes: Combined multi-omics and machine learning strategy - Flavio Agostini; Virginia Baruzzo; Feliciana Real Fernandez; Alessandro Satta; Roberto Raga; Diego Penzo; Michele Modesti; Maria Chiara Valerin; Stefano Campanaro; Laura Treu; Guido Zampieri (Bioresource Technology, 2026)

Olive pomace-derived pectin limits lipid droplet hypertrophy and collagen deposition and is associated with hepatic transcriptional changes in a MASLD murine model - Luna Barrera-Chamorro; Jose L. del-Rio-Vazquez; Africa Fernandez-Prior; Elvira Marquez-Paradas; Carmen M. Claro-Cala; Teresa Gonzalez-de la Rosa; Maria Torrecillas-Lopez; Sergio Montserrat de la Paz (Food Bioscience, 2026)

Oceanic climate variability influences radial growth of Pentaclethra macroloba in the Amazon estuary through local climatic pathways - Adelson Rocha Dantas; Jochen Schöngart; Marcelino Carneiro Guedes; Maria Teresa Fernandez Piedade (Agricultural and Forest Meteorology, 2026)

Optimization of the production of biolubricants from a residual oil by a hydroesterification strategy: Yield-dependent performance evaluation of home-made combi-biocatalyst systems - Rodolpho R.C. Monteiro; Maria M.F. de Melo Neta; Adriano A. Mendes; F. Murilo T. de Luna; Roberto Fernandez-Lafuente; Rodrigo S. Vieira (Sustainable Chemistry and Pharmacy, 2026)

Blue carbon inventories of Spain and Portugal for their inclusion in national climate mitigation strategies - Nerea Piñeiro-Juncal; Oscar Serrano; Carmen B. de los Santos; Nuria Marbà; Elena Díaz-Almela; Fernando Tuya; Inés Mazarrasa; Joxe Mikel Garmendia; Xosé Lois Otero; Karina Inostroza; Jordi F. Pagès; Gonzalo Mendez-Martínez; et al. (Marine Pollution Bulletin, 2026)

Commensal and pathogenic bacteria of the respiratory tract of bats from Catalonia, North-Eastern Spain - Carlotta Pasetto; Lourdes Lobato-Bailón; Maria Puig Ribas; Virginia Aragón; David Guixé; Noel Caparroz-Soto; Jordi Camprodon; Laura Martino; Mariano Domingo; Elena Obón; Rafael Molina-López; Xavier Fernandez Aguilar; et al. (Veterinary Microbiology, 2026)

Beyond solubilization: Interface PAH biodegradation in nonaqueous-phase liquids treated with a plant biosurfactant - Alicia Fernandez-Vazquez; Maria Jordán; Rosa Posada-Baquero; Joaquim Vila; Magdalena Grifoll; Jose-Julio Ortega-Calvo (Journal of Hazardous Materials, 2026)

A new c.681dup RUNX1 variant in familial leukemia - Maria Crocioni; Carlotta Nardelli; Anair Graciela Lema Fernandez; Valentina Bardelli; Valentina Pierini; Caterina Matteucci; Eloise Beggiato; Matteo Olivi; Valentina Vigliani; Alessandra Pelle; Giuseppe Lanzarone; Cristina Mecucci (Familial Cancer, 2026)
Constitutional RUNX1 gene variants are associated with Familial Platelet Disorder (FPD) and predispose to a variety of hematological malignancies, included Acute Myeloid Leukemia (AML) and, albeit less frequently, Acute Lymphoblastic Leukemia (ALL). In this study, we report on a proband with primary diagnosis of AML, followed by T-ALL after transplant, and a positive familial history for leukemia over three generations. A new heterozygous germline pathogenic RUNX1 (c.681dup, p.(Leu228ThrfsTer33)) variant was found in the proband and his affected mother.

How artificial drought generated by the Balbina hydropower dam has transformed the floristic structure of downstream floodplain forests - Carla Iara Dos Santos Dantas; Layon Oreste Demarchi; Florian Wittmann; Maria Teresa Fernandez Piedade; Giuliette Barbosa Mano; João Paulo Martins de Souza; Jochen Schöngart (Forest Ecology and Management, 2026)

Long-term effects of Aloe vera-based hydrochar on earthworm life cycle and soil microbial functions in natural soil - Concepcion Garcia-Gomez; Dimitrios Kalderis; Maria Dolores Fernandez (Applied Soil Ecology, 2026)

Traps as tools for monitoring deep-sea ecosystems and promoting sustainable fishing - Maria Vigo; Ulla Fernandez-Arcaya; Joan Navarro; Maria Valls; Beatriz Guijarro; M. Teresa Farriols; Nixon Bahamón; Guiomar Rotllant; José A. García; Alba Rojas; Enric Massutí; Joan B. Company (Marine Biology Research, 2026)

Ultrasound-assisted recovery of lycopene from tomato waste: a systematic review supported by generative artificial intelligence - Cristina Arroqui; Maria N. Berradre; Idoya Fernandez-Pan; María José Beriain; Francisco C. Ibañez; Paloma Virseda (Trends in Food Science & Technology, 2026)

Vermifiltration for the treatment of water contaminated with acetochlor: A study on the processes’ contributions to its dissipation - Maria Emilia Fernandez; Carolina Elisabet Masin; Agustín Weimer; Eduardo Vidal; María de los Milagros Ballari; Cristina Susana Zalazar (Journal of Environmental Management, 2026)

"MLVA_5: A reduced marker scheme for phylogeographic analysis of Brucella canis" - Eduardo Jorge Boeri; Paula Becker; Silvia Noemi Akiyama; Maria Luz Dominguez; Sebastian Elena; Natalia Mercedes Fernandez; Paula Ruybal; Gabriela Ileana Escobar; Deborah Beatriz Hasan; Marcos David Trangoni (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

HPCCC-guided biorefinery strategy for the scalable recovery and biofunctional evaluation of diadinoxanthin from the diatom Phaeodactylum tricornutum - Daniela Bárcenas-Pérez; Maria Rita Garcia; Nelson G.M. Gomes; Paula B. Andrade; Arantzazu Sierra-Ramirez; Jakub Zápal; Marek Kuzma; Gergely Ernő Lakatos; Martin Lukeš; Pavel Hrouzek; Pablo J. Fernandez-Marcos; José Cheel (Algal Research, 2026)

Bioaccessibility of phloretin and its derivatives using a dynamic in vitro digester. Effects on glucose uptake, bacterial growth and anti-inflammatory activity - Jose L. Gonzalez-Alfonso; Laura Barahona; Sandra Garcia-Benlloch; Maria Martinez-Ranz; Beatriz Gracia-Gomez; Miguel A. Iñiguez; Blanca Viadel; Maria Fernandez-Lobato; Francisco J. Plou (Food Research International, 2026)

Analysis of differential gene expression in dairy cows with high and low superoxide dismutase activity - Calcaterra Francisco; Fernandez Maria Elena; Marcuzzi Olivia; Olivera Leonidas Hernan; Picco Sebastian Julio; Guillermo Giovambattista (Tropical Animal Health and Production, 2026)

The biomedical engineer’s pledge: overview and context - Antoni Ivorra; Txetxu Ausín; Laura Becerra-Fajardo; Antonio J. del Ama; Jesús Minguillón; Aracelys García-Moreno; Jordi Aguiló; Filipe Oliveira Barroso; Bart Bijnens; Oscar Camara; Sara Capdevila; Roger Castellanos Fernandez; et al. (Medical & Biological Engineering & Computing, 2026)
Although biomedical engineering (BME) is a profession with ethical responsibilities comparable to those in medicine, it has, until now, lacked a counterpart to the Hippocratic Oath. While professional societies have established codes of ethics for biomedical engineers, these documents lack the symbolic and ceremonial significance of an oath or pledge. By contrast, the recitation of the Hippocratic Oath, or its modern version, the “Physician’s Pledge,” serves as a powerful rite of passage for medical students, fostering a strong sense of ethical duty at the start of their professional journey. However, the content of the Hippocratic Oath includes elements specific to clinical practice and is not directly applicable to biomedical engineering. To fill this gap, we have created a “Biomedical Engineer’s Pledge,” comprising a preamble, ten promises, and a concluding statement, to inspire ethical awareness and establish a meaningful graduation tradition. Graphical abstract

A novel water pollution index for domestic water quality assessment in acid mine drainage-impacted mining areas - Christian Jay P. Balboa; Joshua P. Pocaan; Ronben Baute; Aileen Orbecido; Arnel B. Beltran; Ana L. Santos; Anne Jungblut; Yves Plancherel; Pablo Brito-Parada; Carlito Baltazar Tabelin; Vannie Joy Resabal; Mylah Villacorte-Tabelin; et al. (Minerals Engineering, 2025)

Long-term impact of oral gestational PM10 exposure on morris water maze performance and hippocampal gene expression - Ruiz-Sobremazas Diego; Coca Mario; Morales-Navas Miguel; Nerea Rios Nieto; Rodulfo-Cárdenas Rocío; Colomina Maria Teresa; López-Granero Caridad; Sanchez-Santed Fernando; Perez-Fernandez Cristian (Environmental Toxicology and Pharmacology, 2025)

Diagnostic Potential of a Recombinant Candida albicans Hyr1 Protein - Marta Bregón-Villahoz; Ander Díez; Jon Galech; Maria-Soledad Cuétara; Giulia Carrano; Maria-Dolores Moragues; Iñigo Fernandez-de-Larrinoa; Inés Arrieta-Aguirre (Mycopathologia, 2025)
Invasive candidiasis (IC) is a life-threatening fungal infection caused by Candida species. Current diagnostic methods are based on blood culture of the fungus, a technique with limited sensitivity and slow turnaround times. To address these limitations, novel diagnostic strategies are under investigation. This study evaluates the diagnostic potential of the Candida albicans germ tube protein Hyr1 and a subterminal Hyr1 fragment (D22b), both produced in an eukaryotic expression system, for the diagnosis of IC; for that purpose, recombinant Hyr1 and D22b were expressed in Pichia pastoris and tested by ELISA using sera from 176 patients at risk of invasive fungal infections. The diagnostic performance of these antigens was determined and compared with other biomarkers (CAGTA and β-D-glucan). Interestingly, the recombinant proteins exhibited higher apparent molecular weights than predicted, suggesting the presence of post-translational modifications. Serological detection of antibodies against the recombinant Hyr1 and D22b fragment successfully distinguished patients with IC caused by the most commonly isolated Candida species, achieving sensitivities greater than 70% and specificities above 80%. These findings highlight the potential of the serological detection of antibodies to Hyr1 and D22b as a promising diagnostic approach that overcomes the drawbacks of CAGTA detection and could serve as a valuable complement to blood culture, supporting earlier diagnosis and guiding timely treatment decisions in IC. Furthermore, comparing results obtained with antigens produced in eukaryotic and prokaryotic systems, results suggest that accurate protein folding and post-translational processing influence the success of the diagnostic technique.

Adaptation and analysis of the psychometric properties of the Chinese version of the MARA questionnaire to assess breast cancer awareness - Jialing Li; Xiaoxia Zhang; Fengying Zhang; Maria del Mar Fernandez-Alvarez; Alvaro Postigo; Ruben Martin-Payo (Cancer Causes & Control, 2025)

Identifying future steps to allow an efficient fisheries management advice among scientific committees in regional fisheries management organizations - Maria Grazia Pennino; Santiago Cerviño; Marta Cousido-Rocha; Ruth Fernandez; Diana Gonzalez-Troncoso; Fernando Gonzalez; Beatriz Guijarro; José Luis Pérez Gil; Maria Soto (Marine Policy, 2025)

Temporal dynamics of minesoil restoration in Southern Brazil: A two-decade monitoring of soil physical attributes and organic carbon content - Maria Bertaso de Garcia Fernandez; Otávio dos Anjos Leal; Gláucia Oliveira Islabão; Adão Pagani Junior; Tainara Vaz de Melo; Ana Paula Knapp; Istefani Wenske Haudt; Emerson Meireles de Farias; Luiz Fernando Spinelli Pinto; Pablo Miguel; Jakeline Rosa de Oliveira; Nicolas Brüggemann; et al. (Soil and Tillage Research, 2025)

A novel calibration of global soil roughness effects for SMOS-IC soil moisture and L-VOD products - Preethi Konkathi; Xiaojun Li; Roberto Fernandez-Moran; Xiangzhuo Liu; Zanpin Xing; F. Frappart; Maria Piles; L. Karthikeyan; Jean-Pierre Wigneron (Remote Sensing of Environment, 2025)

Assessing Volatile Organic Compounds (VOCs) in a laboratory and office building environment - Hector Garcia-Gonzalez; Maria Teresa Lopez-Pola; Rafael Rodriguez; Pilar Fernandez-Rubio; Pablo Fernandez-Rodriguez (Air Quality, Atmosphere & Health, 2025)

The spread of Aoroides longimerus Ren & Zheng, 1996 across the Mediterranean and the Atlantic: genetic diversity, anthropogenic transport, and ecological implications - JOSÉ MANUEL GUERRA-GARCÍA; ANDREA DESIDERATO; SERENA MUCCIOLO; CARLOS NAVARRO-BARRANCO; MACARENA ROS; JASMINE FERRARIO; PAULA MORETTI; AGNESE MARCHINI; NAWFEL MOSBAHI; SOFÍA RUIZ-VELASCO; IGNACIO GESTOSO; PATRÍCIO RAMALHOSA; et al. (Mediterranean Marine Science, 2025)
Accurate knowledge of the global distribution of non-indigenous species (NIS) is essential for understanding their invasion dynamics and for implementing timely management measures. This study reports the first records of the marine amphipod Aoroides longimerus, putatively native to the East Asian coast, in Italy (2018), Spain (2019) and Tunisia (2022) and provides the earliest documented record of the species in its introduced European range (Portugal, 2011). Furthermore, it expands the species’ known distribution in mainland Portugal (including the northernmost record), Macaronesia (with first records in the Canary Islands and Madeira), and confirms its presence along the Atlantic coasts of France and the Netherlands. Aquaculture facilities, particularly those associated with oyster farming, are probably the primary vector of introduction, while recreational boating may have contributed significantly to secondary dispersal. In comparison to other exotic amphipods, A. longimerus remains absent from many marinas, ports and/or aquaculture facilities in the Mediterranean Sea and adjacent regions, such as the Red Sea. This suggests that the species may still be in the early stages of expansion, or that its dispersal ability across marinas and ports is more limited than that of other amphipods. The present study, however, highlights several key ecological traits of A. longimerus: (i) it can survive year-round despite seasonal fluctuations, and reach high local densities, (ii) it exhibits strong colonisation capacity, as shown by its rapid establishment on settlement plates, and (iii) it displays opportunistic feeding behaviour, primarily consuming detritus. These characteristics underscore the importance of continuous surveillance and effective communication with stakeholders to prevent further expansion of this species.

Implementation of an Educational Intervention for Gastric Cancer Awareness in the General Population in CELAC and Europe: A Strategy Proposed by the LEGACy Consortium - Juan Antonio Carbonell-Asins; Elena Jiménez-Martí; Sergio Romero; Eduardo García; Ana Miralles-Marco; Beatriz Lopez; Marisol Huerta; Carmelo Caballero; Hugo Boggino; Cinthia Gauna; Olga Beatriz Acevedo-Funes; Gabriel Benitez Nuñez; et al. (Journal of Cancer Education, 2025)
Gastric cancer (GC) has a poor prognosis. The LEGACy consortium has been established to enhance GC outcomes though improved primary and secondary prevention strategies. We performed an educational intervention study using an online module to disseminate knowledge about GC risk factors and symptoms to the general population. Participants were recruited through various media channels and were exposed to an online questionnaire to assess their knowledge, before and after the educational intervention. The educational intervention included an informative brochure and a short video providing essential information about GC. Primary outcome was to evaluate the overall knowledge (global score) before and after the intervention. A total of 1034 participants were evaluated before the intervention. Of those, 866 also completed the short-term and 362 the long-term questionnaire after the intervention, respectively. On a scale of 0 to 17, the baseline global score mean was 9.4 (3.2). Results showed an increase in the average global knowledge score by 1.80 (95% CI: 1.63–1.96, p < 0.001) and 1.81 (95% CI: 1.65–1.96, p < 0.001) points after completing the short and long-term questionnaires compared to the baseline respectively for all individual questions ( p < 0.05). This interventional study showed significantly improved knowledge in most domains on GC risk factors, signs, and symptoms which could be a useful strategy for promoting cancer prevention. ClinicalTrials.gov Identifier: NCT04019808.

Adsorption, degradation, and synergistic effects of pesticides in biomixtures containing vermicompost from agricultural and urban waste - Aldana Carolina Clebot; Florencia Valentina Magni; Maria Rosa Repetti; Cristina Susana Zalazar; Maria Emilia Fernandez (Journal of Water Process Engineering, 2025)

Building a multidisciplinary database across cultures: lessons from the Mongolian Rangelands and Resilience (MOR2) Project - Khishigbayar Jamiyansharav; Melinda J. Laituri; Mara Sedlins; Tobin Magle; Maria Fernandez-Gimenez; Sophia Linn; Steven R. Fassnacht; Niah Venable; Tungalag Ulambayar; Arren Mendezona Allegretti; Chantsallkham Jamsranjav; Robin Reid (Frontiers of Earth Science, 2025)

Dynamic Changes in Oxidative Stress and Epigenetic Modifications in the Ventral Mesencephalon and Striatum of MPTP-Treated Mice: Implications for Parkinson's Disease Pathogenesis - Pablo Gallo-Soljancic; Maria Egle De Stefano; Ana-Maria Gonzalez-Cuello; Emiliano Fernandez-Villalba; Lode Godderis; Maria Trinidad Herrero (Neurotoxicity Research, 2025)
This study investigates the effects of an acute 1-metil 4-fenil 1,2,3,6-tetraidro-piridina (MPTP) treatment, a known inducer of parkinsonism, on oxidative stress and epigenetic changes in the mouse ventral midbrain (VM) and striatum. Key markers were analyzed at 4, 8, 24, and 48 h post-injections: the hydroxylated form of the purine guanine (8-hydroxy-2'-deoxyguanosine; 8-OHdG), a marker of oxidative stress; the methylated form of cytosine (5-methylcytosine; 5-mC), associated with gene silencing; the hydroxy methylated form of cytosine (5-hydroxymethylcytosine; 5-hmC), involved in demethylation and gene regulation. The results showed a pronounced decrease in 8-OHdG levels in the VM, suggesting a rapid oxidative stress response, whereas the striatum exhibited a less pronounced response, reflecting regional differences in oxidative stress vulnerability DNA methylation patterns revealed complex and biphasic changes in 5-mC levels in the VM, contrasted with a less pronounced response in the striatum, suggesting disrupted methylation homeostasis and regional epigenetic variability. MPTP treatment also significantly reduced in 5-hmC levels in the VM, pointing to impaired active DNA demethylation and compromised epigenetic flexibility. In contrast, the striatum maintained consistently high 5-hmC levels, reflecting compensatory hydroxymethylation mechanisms specific to this region. These findings highlight pronounced regional differences in oxidative stress vulnerability and epigenetic regulation, with the VM showing heightened sensitivity to oxidative damage and impaired epigenetic flexibility. This underscores the importance of understanding the role of oxidative and epigenetic mechanisms in Parkinson’s disease pathophysiology, The changes pave the way for novel therapeutic strategies targeting oxidative DNA damage and epigenetic homeostasis.

Ecological transcriptomics reveals stress response pathways of a ground‐herb species in a waterlogging gradient of Amazonian riparian forests - Clarisse Palma‐Silva; Amanda F. Mortati; Cleber Juliano Neves Chaves; Bárbara Simões Santos Leal; Rafael V. Ribeiro; Fabio Pinheiro; Milene Ferro; Diego M. Riaño‐Pachón; Jacqueline Salvi de Mattos; Marília Manupella Tavares; Paulo Aecyo; Tami da Costa Cacossi; et al. (Molecular Ecology, 2025)
Environmental stress is a fundamental facet of life and a significant driver of natural selection in the wild. Gene expression diversity may facilitate adaptation to environmental changes, without necessary genetic change, but its role in adaptive divergence remains largely understudied in Neotropical systems. In Amazonian riparian forests, species distribution is predominantly influenced by species' waterlogging tolerance. The flooding gradient delineates distinct wetland forest types, shaping habitats and species characteristics. Here we investigated the molecular basis of environmental stress response in a tropical ground‐herb species ( Ischnosiphon puberulus ) to environmental variation in Amazonian riparian forests. We compared environmental variables and gene expression profiles from individuals collected in two forest types: Igapó and Terra firme in the Amazonian riparian forests. Predictable seasonal flooding poses a significant challenge in Igapó compared to Terra firme environments, with the former presenting higher water column height and longer flooding duration. Our findings suggest that contrasting environmental conditions related to flooding regimes are important drivers of population genetic differentiation and differential gene expression in I. puberulus . Enriched gene ontology terms highlight associations with environmental stresses, such as defence response, water transport, phosphorylation, root development, response to auxin, salicylic acid and oxidative stress. By uncovering key environmental stress response pathways conserved across populations, I. puberulus offers novel genetic insights into the molecular basis of plant reactions to environmental constraints found in flooded areas of this highly biodiverse neotropical ecosystem.

Changes in community composition and functional diversity of European bats under climate change - Penelope C. Fialas; Luca Santini; Danilo Russo; Francisco Amorim; Hugo Rebelo; Roberto Novella‐Fernandez; Francisco Marques; Adi Domer; Adriana Vella; Adriano Martinoli; Aleksandra Figurek; Asaf Tsoar; et al. (Conservation Biology, 2025)
Climate change is predicted to drive geographical range shifts that will result in changes in species diversity and functional composition and have potential repercussions for ecosystem functioning. However, the effect of these changes on species composition and functional diversity (FD) remains unclear, especially for mammals, specifically bats. We used species distribution models and a comprehensive ecological and morphometrical trait database to estimate how projected future climate and land‐use changes could influence the distribution, composition, and FD of the European bat community. Future bat assemblages were predicted to undergo substantial shifts in geographic range and trait structure. Range suitability decreased substantially in southern Europe and increased in northern latitudes. Our findings highlight the potential for climate change to drive shifts in bat FD, which has implications for ecosystem function and resilience at a continental scale. It is important to incorporate FD in conservation strategies. These efforts should target species with key functional traits predicted to be lost and areas expected to experience losses in FD. Conservation strategies should include habitat and roost protection, enhancing landscape connectivity, and international monitoring to preserve bat populations and their ecosystem services.

Wavelet analysis and sinusoidal modelling of environmental variables in a weaned piglet farm - Maria D. Fernandez; Manuel R. Rodriguez; Xose R. Fdez-Vidal; Roberto Besteiro (Building and Environment, 2025)

Personal exposure to particulate matter oxidative potential and airway inflammation: differences between asthmatic and non-asthmatic adults - Miguel Santibáñez; Juan José Ruiz-Cubillán; Juan Agüero; Andrea Expósito; Beatriz Abascal; Juan Luis García-Rivero; Carlos Antonio Amado; Maria Mercedes Hernando; Laura Ruiz-Azcona; Esther Barreiro; Adriana Núñez-Robainas; José Manuel Cifrián; et al. (International Journal of Hygiene and Environmental Health, 2025)

Fish Assemblage Characteristics and Allochthonous Food Resources Shape the Topology of Trophic Networks in Blackwater Floodplain Forests - Bianca Weiss; Fernanda Costa; Flavia Santana; Viviane Pagnussat Klein; Aline Lopes; Gilvan Costa; Jochen Schöngart; Florian Wittmann; Flavia Durgante; Jansen Zuanon; Maria Teresa Fernandez Piedade (Wetlands, 2025)

In Vitro Influence of Specific Bacteroidales Strains on Gut and Liver Health Related to Metabolic Dysfunction-Associated Fatty Liver Disease - Diego Garcia-Morena; Maria Victoria Fernandez-Cantos; Silvia Lopez Escalera; Johnson Lok; Valeria Iannone; Pierluca Cancellieri; Willem Maathuis; Gianni Panagiotou; Carmen Aranzamendi; Sahar El Aidy; Marjukka Kolehmainen; Hani El-Nezami; et al. (Probiotics and Antimicrobial Proteins, 2025)
Metabolic dysfunction-associated fatty liver disease (MAFLD) has become a major health risk and a serious worldwide issue. MAFLD typically arises from aberrant lipid metabolism, insulin resistance, oxidative stress, and inflammation. However, subjacent causes are multifactorial. The gut has been proposed as a major factor in health and disease, and over the last decade, bacterial strains with potentially beneficial effects on the host have been identified. In vitro cell models have been commonly used as an early step before in vivo drug assessment and can confer complementary advantages in gut and liver health research. In this study, several selected strains of the order Bacteroidales were used in a three-cell line in vitro analysis (HT-29, Caco-2, and HepG2 cell lines) to investigate their potential as new-generation probiotics and microbiota therapeutics. Antimicrobial activity, a potentially useful trait, was studied, and the results showed that Bacteroidales can be a source of either wide- or narrow-spectrum antimicrobials targeting other closely related strains. Moreover, Bacteroides sp. 4_1_36 induced a significant decrease in gut permeability, as evidenced by the high TEER values in the Caco-2 monolayer assay, as well as a reduction in free fatty acid accumulation and improved fatty acid clearance in a steatosis HepG2 model. These results suggest that Bacteroidales may spearhead the next generation of probiotics to prevent or diminish MAFLD.

Hydrological Connectivity Enhances Fish Biodiversity in Amazonian Mining Ponds: Insights From eDNA and Traditional Sampling - Camila Timana‐Mendoza; Alonso Reyes‐Calderón; Patrick Venail; Ricardo Britzke; Monica C. Santa‐Maria; Julio M. Araújo‐Flores; Miles Silman; Luis E. Fernandez (Molecular Ecology, 2025)
Artisanal and small‐scale gold mining (ASGM) expansion in the Madre de Dios region of the Peruvian Amazon has transformed primary forests into a novel wetland complex of thousands of abandoned mining ponds. Despite their ecological relevance, post‐mining recovery of these systems remains understudied, particularly regarding fish biodiversity and recolonisation. In this study, we evaluate fish community richness and composition in mining ponds of different dimensions, years post abandonment, physicochemical properties and degree of pulse flood connectivity using traditional collection‐based methods and environmental DNA (eDNA) with the 12S and COI markers. We compared these two methods of biodiversity inventory and contrasted results from ASGM waterbodies with those obtained from nearby pristine oxbow lakes. Overall, we registered more fish richness at all sites using eDNA versus traditional methods, especially with the 12S marker. We identified 14 and 13 unique genera using traditional methods and eDNA, respectively, with 40 genera detected by both approaches, evidencing their complementarity. Notably, we found that the degree of pulse flooding connectivity was the main predictor of species richness among the abandoned mining ponds ( p ‐value

The effects of oral gestational particulate matter 10 exposure: Insights into neurodevelopmental milestones, inhibitory control, adult sociability, and object recognition - Diego Ruiz-Sobremazas; Mario Coca; Miguel Morales-Navas; Rocío Rodulfo-Cardenas; Caridad Lopez-Granero; Maria-Teresa Colomina; Cristian Perez-Fernandez; Fernando Sanchez-Santed (NeuroToxicology, 2025)

Characterization of Rugulopteryx okamurae algae: A source of bioactive peptides, omega-3 fatty acids, and volatile compounds - Fernando Rivero-Pino; Teresa Gonzalez-de la Rosa; Maria Torrecillas-Lopez; Luna Barrera-Chamorro; Jose Luis del Rio-Vazquez; Elvira Marquez-Paradas; Africa Fernandez-Prior; Marco Garcia-Vaquero; Jose Carlos Garcia-Gomez; Sergio Montserrat-de la Paz; Carmen Maria Claro-Cala (Food Chemistry, 2025)

Narratives for Positive Nature Futures in Europe - Alessandra D’Alessio; Claudia Fornarini; Nestor Fernandez; Anandi Sarita Namasivayam; Piero Visconti; Jeremy Dertien; Maria Hällfors; Martin Jung; Francisco Moreira; Louise O’Connor; Matea Osti; Laura C. Quintero-Uribe; et al. (Environmental Management, 2025)
The Nature Futures Framework (NFF) is a novel approach for the development of positive scenarios centered on the relationship of nature and people, emphasizing biodiversity as part of the solution to environmental challenges across various spatial and temporal scales, explicitly addressing a plurality of values for nature. In this work, we describe the process that has led to the formulation of continental-scale positive narratives for conservation in Europe based on the NFF and its value perspectives (Nature for Nature; Nature for Society; Nature as Culture), through an expert group elicitation. We focused on 6 topics in the narratives: Nature Protection and Restoration; Forest Ecosystems; Freshwater Ecosystems; Urban Systems; Agriculture, and Energy. We analyze differences and similarities among the narratives across these topics. We develop three novel Nature Futures narratives for Europe with contrasting perspectives and priorities for the six topics. Within the EU socioeconomic trends and policy framework, common solutions that simultaneously tackle biodiversity conservation and instrumental and cultural Nature’s Contributions to People (NCP) provision emerged. This set of narratives may integrate preferences concerning EU-level conservation targets and plausible socio-ecological development pathways, supporting the modeling of positive scenarios for nature that can be crucial in guiding policy decisions towards recovery of nature.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Corrigendum to “A forecasting model for desert locust presence during recession period, using real-time satellite imagery” [Remote Sens. Appl.: Soc. Environ. (37) 101497] - Lucile Marescot; Elodie Fernandez; Hichem Dridi; Ahmed Salem Benahi; Mohamed Lemine Hamouny; Koutaro Ould Maeno; Maria-José Escorihuela; Giovanni Paolini; Cyril Piou (Remote Sensing Applications: Society and Environment, 2025)

European sustainability reporting standards: An assessment of requirements and preparedness of EU companies - Walter Leal Filho; Tony Wall; Kent Williams; Maria Alzira Pimenta Dinis; Rosa Maria Fernandez Martin; Muhammad Mazhar; Andrea Gatto (Journal of Environmental Management, 2025)

Abundance and diversity of mesofauna in relation to minesoil properties after 14.6 years of revegetation with grasses - Mauricio Silva Oliveira; Otávio dos Anjos Leal; Maria Bertaso de Garcia Fernandez; Nicolas Brüggemann; Pablo Miguel; Luiz Fernando Spinelli Pinto; Jakeline Rosa de Oliveira; Gláucia Oliveira Islabão; Lizete Stumpf (Ecological Engineering, 2025)

Glycogen Synthase Kinase-3β Inhibitor VP3.15 Ameliorates Neurogenesis, Neuronal Loss and Cognitive Impairment in a Model of Germinal Matrix-intraventricular Hemorrhage of the Preterm Newborn - Isabel Atienza-Navarro; Angel del Marco; Pilar Alves-Martinez; Maria de los Angeles Garcia-Perez; Alvaro Raya-Marin; Isabel Benavente-Fernandez; Carmen Gil; Ana Martinez; Simon Lubian-Lopez; Monica Garcia-Alloza (Translational Stroke Research, 2025)
Advances in neonatology have significantly reduced mortality rates due to prematurity. However, complications of prematurity have barely changed in recent decades. Germinal matrix-intraventricular hemorrhage (GM-IVH) is one of the most severe complications of prematurity, and these children are prone to suffer short- and long-term sequelae, including cerebral palsy, cognitive and motor impairments, or neuropsychiatric disorders. Nevertheless, GM-IVH has no successful treatment. VP3.15 is a small, heterocyclic molecule of the 5-imino-1,2,4-thiadiazole family with a dual action as a phosphodiesterase 7 and glycogen synthase kinase-3β (GSK-3β) inhibitor. VP3.15 reduces neuroinflammation and neuronal loss in other neurodegenerative disorders and might ameliorate complications associated with GM-IVH. We administered VP3.15 to a mouse model of GM-IVH. VP3.15 reduces the presence of hemorrhages and microglia in the short (P14) and long (P110) term. It ameliorates brain atrophy and ventricle enlargement while limiting tau hyperphosphorylation and neuronal and myelin basic protein loss. VP3.15 also improves proliferation and neurogenesis as well as cognition after the insult. Interestingly, plasma gelsolin levels, a feasible biomarker of brain damage, improved after VP3.15 treatment. Altogether, our data support the beneficial effects of VP3.15 in GM-IVH by ameliorating brain neuroinflammatory, vascular and white matter damage, ultimately improving cognitive impairment associated with GM-IVH.

Upcycling HDPE plastic into value-added products via γ-alumina catalyzed steam cracking in a fountain confined spouted bed - Manomita Mollick; Maria Cortazar; Laura Santamaria; Enara Fernandez; Maite Artetxe; Martin Olazar; Gartzen Lopez (Journal of Environmental Chemical Engineering, 2025)

Promoting Workplace Health, Safety, and Well-Being Among Essential Agricultural Workers Through Vaccine-Preventable Infectious Diseases Training in the Rio Grande Valley - Anabel Rodriguez; David I Douphrate; Ana L Pineda Reyes; Susana Zavala; Andrea V. Cabrera Cruz; Maria D Alegria; Brian Ukaegbu; Annie J Keeney; Brenda Berumen-Flucker; Eva M Shipp; Shannon P Guillot-Wright; Maria E Fernandez-Esquer; et al. (Journal of Agromedicine, 2025)

A forecasting model for desert locust presence during recession period, using real-time satellite imagery - Lucile Marescot; Elodie Fernandez; Hichem Dridi; Ahmed Salem Benahi; Mohamed Lemine Hamouny; Koutaro Ould Maeno; Maria-José Escorihuela; Giovanni Paolini; Cyril Piou (Remote Sensing Applications: Society and Environment, 2025)

Properties and medical applications of the Euphorbiaceae family and their bioproducts: a patent review - Laila Maria Barreto Silva; Rodrigo Cunha Oliveira; Dianne Dominguez Formoso; Marta Bruno Loureiro; Luzimar Gonzaga Fernandez (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Bacterial communities forming yellow biofilms in different cave types share a common core - Tamara Martin-Pozas; Valme Jurado; Angel Fernandez-Cortes; Jose Maria Calaforra; Sergio Sanchez-Moral; Cesareo Saiz-Jimenez (Science of The Total Environment, 2024)

Wastewater-based surveillance for Hepatitis A virus, Enterovirus, Poliovirus, and SARS-CoV-2 in São Tomé and Príncipe: A pilot study - Katia Toancha; Adjaia Borges; Lazismino Lázaro; Nilton Teixeira; Anery Katia Lima; Anabela Gonçalves; Doris Winter; Asmiralda Santos; Marcos do Nascimento; Andreza Batista de Sousa; Jürgen May; Yardlene Sacramento Sequeira; et al. (Science of The Total Environment, 2024)

A giant gardener of the Floodplains: The Amazonian manatee - Michelle Gil Guterres-Pazin; Aline Lopes; Victor Fernando Volpato Pazin; Denise Garcia de Santana; Miriam Marmontel; Maria Teresa Fernandez Piedade (Journal for Nature Conservation, 2024)

Geostatistical modeling of the rainfall patterns and monthly multiscale characterization of drought in the South Coast of the Northeast Brazilian via Standardized Precipitation Index - Marcos Vinícius da Silva; Jhon Lennon Bezerra da Silva; Maria Beatriz Ferreira; Lizandra de Barros de Sousa; Abelardo Antônio de Assunção Montenegro; Jorge Manuel Guieiro Pereira Isidoro; Héliton Pandorfi; José Francisco de Oliveira-Júnior; Helena Maria Neto Paixão Vazquez Fernandez; Fernando Miguel Granja-Martins; Alexandre Maniçoba da Rosa Ferraz Jardim; Thieres George Freire da Silva; et al. (Atmospheric Research, 2024)

Unraveling autonomic cardiovascular control complexity during orthostatic stress: Insights from a mathematical model - Martin Miranda Hurtado; Rafael Kaempfer; Justen R. Geddes; Mette S. Olufsen; Maria Rodriguez-Fernandez (Mathematical Biosciences, 2024)

Nutritional characterization of aquatic plants in different floodplain habitats of the Central Amazon - Michelle Gil Guterres-Pazin; Maria Teresa Fernandez Piedade; Miriam Marmontel; Fernando César Weber Rosas; Ludmilla Geraldo Di Santo; Victor Fernando Volpato Pazin; Aline Lopes (Hydrobiologia, 2024)

A multimethod interpolation approach for mapping the spatial distribution of rainfall in southwest Iberian Peninsula - Verónica Ruiz-Ortiz; Helena Maria Fernandez; Fernando M. Granja-Martins; Mercedes Vélez-Nicolás; Jorge M. G. P. Isidoro; Santiago García-López (Hydrological Sciences Journal, 2024)

Bio-transformation of poultry litter and activated sewage sludge to produce biomixtures for the remediation of water polluted with pesticides - Aldana Carolina Clebot; Maria Emilia Fernandez; Florencia Valentina Magni; Maria Rosa Repetti; Cristina Susana Zalazar (Chemosphere, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Vermifiltration for removal of emerging contaminant EDTA (ethylenediaminetetraacetic acid). Kinetics models for adsorption, bio- and vermidegradation - Carolina Masin; Eduardo Vidal; Maria Emilia Fernandez; María de los Milagros Ballari; Cristina Zalazar (Journal of Environmental Chemical Engineering, 2024)

Trophic ecology of two non-native cyprinid fish, the common carp Cyprinus carpio and the bleak Alburnus alburnus - Paride Balzani; Mladen Avramović; Antonio Delgado; Phillip J. Haubrock; Antonín Kouba; Maria Fernandez; Agustin P. Monteoliva (Hydrobiologia, 2024)

Clinical characteristics, predisposing factors and outcomes for Enterococcus faecalis versus Enterococcus faecium bloodstream infections: a prospective multicentre cohort study - Fenna Scharloo; Francesco Cogliati Dezza; Inmaculada López-Hernández; Pedro María Martínez Pérez-Crespo; Ane Josune Goikoetxea Aguirre; María Teresa Pérez-Rodríguez; Jonathan Fernandez-Suarez; Eva León Jiménez; Miguel Ángel Morán Rodríguez; Isabel Fernández-Natal; José María Reguera Iglesias; Clara Natera Kindelán; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purposes Enterococcal BSI is associated with significant morbidity and mortality, with fatality rates of approximately 20–30%. There are microbiological and clinical differences between E. faecalis and E. faecium infections. The aim of this study was to investigate differences in predisposing factors for E. faecalis and E. faecium BSI and to explore prognostic factors. Methods This study was a post-hoc analysis of PROBAC, a Spanish prospective, multicenter, cohort in 2016–2017. Patients with E. faecalis or E. faecium BSI were eligible. Independent predictors for BSI development in polymicrobial and monomicrobial BSI and in-hospital mortality in the monomicrobial group were identified by logistic regression. Results A total of 431 patients were included. Independent factors associated with E. faecium BSI were previous use of penicillins (aOR 1.99 (95% CI 1.20–3.32)) or carbapenems (2.35 (1.12–4.93)), hospital-acquired BSI (2.58 (1.61–4.12)), and biliary tract source (3.36 (1.84–6.13)), while congestive heart failure (0.51 (0.27–0.97)), cerebrovascular disease (0.45 (0.21–0.98)), and urinary tract source (0.49 (0.26–0.92)) were associated with E. faecalis BSI. Independent prognostic factors for in-hospital mortality in E. faecalis BSI were Charlson Comorbidity Index (1.27 (1.08–1.51)), SOFA score (1.47 (1.24–1.73)), age (1.06 (1.02–1.10)), and urinary/biliary source (0.29 (0.09–0.90)). For E. faecium BSI, only SOFA score (1.34 (1.14–1.58) was associated with in-hospital mortality. Conclusions The factors associated with E. faecium and E. faecalis BSI are different. These variables may be helpful in the suspicion of one or other species for empiric therapeutic decisions and provide valuable information on prognosis.

Beyond the target species - Implications of microalgal succession and associated microbiome in industrial-scale photobioreactors - Leonardo Rubi Rörig; André Oliveira de Souza Lima; José Bonomi-Barufi; Ellen Junker; Maria Eduarda Castro do Nascimento; Ainoa Morillas-España; Roberto Teófilo Abdala-Diaz; Julia Vega; Antonio Avilés; Francisco Gabriel Acién-Fernandez; Félix López Figueroa (Algal Research, 2024)

In vivo evidences of the health-promoting properties of bioactive compounds obtained from olive by-products and their use as food ingredient - Fernando Rivero-Pino; Maria C. Millan-Linares; Alvaro Villanueva-Lazo; África Fernandez-Prior; Sergio Montserrat-de-la-Paz (Critical Reviews in Food Science and Nutrition, 2024)

Combination of toxicological and epidemiological approaches for estimating the health impact of atmospheric pollutants. A proof of concept for NO2 - Susana Pallarés Porcar; Francisco Javier Sánchez-Íñigo; Beatriz Nuñez-Corcuera; Joaquín Lozano Suárez; Sonia Arca-Lafuente; Clara Moyano Cárdaba; Ana Fernandez Agudo; Mercedes de Alba-Gonzalez; Rebeca Ramis; David Galán-Madruga; Maria del Carmen González-Caballero; Verónica Briz; et al. (Chemosphere, 2024)

Ozone therapy by rectal insufflation in dogs: safety and oxidative stress - a randomized cross-over study - Paula Lima de Oliveira; Mariana Orlandini Mendonça; Geovanna Santos Gonçalves; Isadora Gimenez Franco; Daniela Ribas Jané; Tainara de Oliveira Martins; Maria Rachel Melo Bosculo; Daniela Fernandez Montechiesi; Vinicius Aquiles Gomes Zamboni; Beatriz Perez Floriano; Breno Fernando Martins de Almeida (Veterinary Research Communications, 2024)

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Nudges in sustainable water management practices: Implementation, key findings and research agenda - Marie-Estelle Binet; Maria A. Garcia-Valiñas; Sara Suarez-Fernandez (Journal of Cleaner Production, 2024)

Decomposing drivers in avian insectivory: Large‐scale effects of climate, habitat and bird diversity - Laura Schillé; Elena Valdés‐Correcher; Frédéric Archaux; Flavius Bălăcenoiu; Mona Chor Bjørn; Michal Bogdziewicz; Thomas Boivin; Manuela Branco; Thomas Damestoy; Maarten de Groot; Jovan Dobrosavljević; Mihai‐Leonard Duduman; et al. (Journal of Biogeography, 2024)
Aim Climate is a major driver of large‐scale variability in biodiversity, as a likely result of more intense biotic interactions under warmer conditions. This idea fuelled decades of research on plant‐herbivore interactions, but much less is known about higher‐level trophic interactions. We addressed this research gap by characterizing both bird diversity and avian predation along a climatic gradient at the European scale. Location Europe. Taxon Insectivorous birds and pedunculate oaks. Methods We deployed plasticine caterpillars in 138 oak trees in 47 sites along a 19° latitudinal gradient in Europe to quantify bird insectivory through predation attempts. In addition, we used passive acoustic monitoring to (i) characterize the acoustic diversity of surrounding soundscapes; (ii) approximate bird abundance and activity through passive acoustic recordings; and (iii) infer both taxonomic and functional diversity of insectivorous birds from recordings. Results The functional diversity of insectivorous birds increased with warmer climates. Bird predation increased with forest cover and bird acoustic activity but decreased with mean annual temperature and functional richness of insectivorous birds. Contrary to our predictions, climatic clines in bird predation attempts were not directly mediated by changes in insectivorous bird diversity or acoustic activity, but climate and habitat still had independent effects on predation attempts. Main Conclusions Our study supports the hypothesis of an increase in the diversity of insectivorous birds towards warmer climates but refutes the idea that an increase in diversity would lead to more predation and advocates for better accounting for activity and abundance of insectivorous birds when studying the large‐scale variation in insect‐tree interactions.

New constraints on the Middle-Late Pleistocene Campi Flegrei explosive activity and Mediterranean tephrostratigraphy (∼160 ka and 110–90 ka) - Giada Fernandez; Biagio Giaccio; Antonio Costa; Lorenzo Monaco; Sébastien Nomade; Paul G. Albert; Alison Pereira; Molly Flynn; Niklas Leicher; Federico Lucchi; Paola Petrosino; Danilo M. Palladino; et al. (Quaternary Science Reviews, 2024)

An actor-centered, scalable land system typology for addressing biodiversity loss in the world’s tropical dry woodlands - Marie Pratzer; Patrick Meyfroidt; Marina Antongiovanni; Roxana Aragon; Germán Baldi; Stasiek Czaplicki Cabezas; Cristina A. de la Vega-Leinert; Shalini Dhyani; Jean-Christophe Diepart; Pedro David Fernandez; Stephen T. Garnett; Gregorio I. Gavier Pizarro; et al. (Global Environmental Change, 2024)

Adaptive response of prokaryotic communities to extreme pollution flooding in a Paleolithic rock art cave (Pindal Cave, northern Spain) - Tamara Martin-Pozas; Soledad Cuezva; Angel Fernandez-Cortes; Maria Gonzalez-Pumariega; Javier Elez; Elsa Duarte; Marco de la Rasilla; Juan Carlos Canaveras; Cesareo Saiz-Jimenez; Sergio Sanchez-Moral (Science of The Total Environment, 2024)

Riparian wetlands of low-order streams in Brazil: extent, hydrology, vegetation cover, interactions with streams and uplands, and threats - Wolfgang J. Junk; Maria Teresa Fernandez Piedade; Jochen Schöngart; Catia Nunes da Cunha; Stela Rosa Amaral Goncalves; Karl Matthias Wantzen; Florian Wittmann (Hydrobiologia, 2024)
Low-order streams and riparian wetlands are important contributors to the drainage network in the landscape. However, there has been little research into the nature of these ecosystems in Brazil. Our estimates show that riparian wetlands of low-order streams and other small associated wetlands cover at least 25% of the forested part of the Amazon basin and about 10% of the Cerrado region. Information on the semi-arid Caatinga is lacking, but ~ 3% of the area may be occupied by riparian wetlands and other small wetland types, many of which are periodically dry. Riparian vegetation includes a very large richness in tree species. The amount and species richness of herbaceous plants depend on light availability. In-streams of the semi-arid region of Brazil, hydrophytes are restricted by unpredictable flash floods and periodic drought. Aquatic food webs are largely based on the organic matter produced by the riparian vegetation. Large-scale agriculture and cattle ranching pose a serious threat to riparian wetlands, their biodiversity, and their function as a buffer in the hydrological cycle of the landscape. A nation-wide screening program would provide a more detailed picture and allow the elaboration of a national conservation and restoration program for the Brazilian riparia.

A novel molecule reduces cocoon production loss in BmNPV-infected Bombyx mori larvae - Jully Jesus De La Cruz Cisneros; Lucas Costa Cabral; Daniel Caligari; Alessandra Aparecida Silva; Alex Sandro Gularte Chiarello; Lucinéia de Fátima Chasko Ribeiro; Rose Meire Costa; Adriana Aparecida Sinópolis Gigliolli; Ana Silvia Lapenta; Anelise Cardoso Ramos; Flávio Augusto Vicente Seixas; Maria Aparecida Fernandez (International Journal of Tropical Insect Science, 2024)

Light and dispersal strategies structure palm community along an elevation gradient in the Atlantic Forest - Sara Lucía Colmenares-Trejos; Rita de Cássia Quitete Portela; Alexandra Pires Fernandez; Maria Isabel Guedes Braz; Eduardo Arcoverde de Mattos (Brazilian Journal of Botany, 2024)

Islands in the middle of the forest: size, distance and tree structure drive vascular epiphytes composition in Amazonia white-sand ecosystems - Viviane Pagnussat Klein; Talitha Mayumi Francisco; Layon Oreste Demarchi; Jeisiane Santos da Silva; Adriano Costa Quaresma; Maria Teresa Fernandez Piedade (Brazilian Journal of Botany, 2024)

Evaluation of the management potential of timber resources in clearwater floodplain forests in the Amazon using growth models - Maíra Luciana Guimarães Conde; Maria Teresa Fernandez Piedade; Florian Wittmann; Rodrigo Geroni Mendes Nascimento; Jochen Schöngart (Journal of Environmental Management, 2024)

Larger Fish Disperse Larger Seeds in Oligotrophic Wetlands of the Central Amazon - Gilvan Costa; Bianca Weiss; Maria Teresa Fernandez Piedade (Wetlands, 2024)

Tree growth performance and xylem functional arrangements of Macrolobium Schreb. (Fabaceae) in different wetland forests in the Central Amazon basin - Yanka Laryssa Almeida Alves; Flavia Machado Durgante; Maria Teresa Fernandez Piedade; Florian Wittmann; Jochen Schӧngart (Trees, 2024)

Large diameters and tree bark physical attributes drive vascular epiphyte-phorophyte relationships in Amazonian black-water floodplain forest - Jeisiane Santos da Silva; Maria Teresa Fernandez Piedade; Viviane Pagnussat Klein; Flávia Machado Durgante; Florian Wittmann; Adriano Costa Quaresma (Plant Ecology, 2024)

Identification of volatile organic compounds and their sources driving ozone and secondary organic aerosol formation in NE Spain - Marten in 't Veld; Roger Seco; Cristina Reche; Noemi Pérez; Andres Alastuey; Miguel Portillo-Estrada; Ivan A. Janssens; Josep Peñuelas; Marcos Fernandez-Martinez; Nicolas Marchand; Brice Temime-Roussel; Xavier Querol; et al. (Science of The Total Environment, 2024)

Neurodevelopmental consequences of gestational exposure to particulate matter 10: Ultrasonic vocalizations and gene expression analysis using a bayesian approach - Diego Ruiz-Sobremazas; Mario Ruiz Coca; Miguel Morales-Navas; Rocío Rodulfo-Cárdenas; Caridad López-Granero; Maria Teresa Colomina; Cristian Perez-Fernandez; Fernando Sanchez-Santed (Environmental Research, 2024)

The impact of body mass index and physical disability on home-based anal self-sampling - Jenna Nitkowski; Maria E. Fernandez; Tim Ridolfi; Elizabeth Chiao; Anna R. Giuliano; Vanessa Schick; Michael D. Swartz; Jennifer S. Smith; Alan G. Nyitray (Cancer Causes & Control, 2024)

Diel vertical migration of copepods in the tropical and subtropical Atlantic Ocean - Maria Luz Fernandez de Puelles; Magdalena Gazá; Mar Santandreu; Santiago Hernández-León (Progress in Oceanography, 2023)

The effectiveness of ichthyochoric dispersal in forested wetlands of the Amazon depends on the species of fish and its size - Gilvan Costa; Maria Teresa Fernandez Piedade; Efrem Jorge Ferreira; Leonardo Maltchik (Forest Ecology and Management, 2023)

Twenty years of capacity building across the cancer prevention and control research network - Mary Wangen; Cam Escoffery; Maria E. Fernandez; Daniela B. Friedman; Peggy Hannon; Linda K. Ko; Annette E. Maxwell; Courtney Petagna; Betsy Risendal; Catherine Rohweder; Jennifer Leeman (Cancer Causes & Control, 2023)
Purpose To improve population health, community members need capacity (i.e., knowledge, skills, and tools) to select and implement evidence-based interventions (EBIs) to fit the needs of their local settings. Since 2002, the Centers for Disease Control and Prevention has funded the national Cancer Prevention and Control Research Network (CPCRN) to accelerate the implementation of cancer prevention and control EBIs in communities. The CPCRN has developed multiple strategies to build community members’ capacity to implement EBIs. This paper describes the history of CPCRN’s experience developing and lessons learned through the use of five capacity-building strategies: (1) mini-grant programs, (2) training, (3) online tools, (4) evidence academies, and (5) evaluation support for partners’ capacity-building initiatives. Methods We conducted a narrative review of peer-reviewed publications and grey literature reports on CPCRN capacity-building activities. Guided by the Interactive Systems Framework, we developed histories, case studies, and lessons learned for each strategy. Lessons were organized into themes. Results Three themes emerged: the importance of (1) community-engagement prior to and during implementation of capacity-building strategies, (2) establishing and sustaining partnerships, and (3) co-learning at the levels of centers, networks, and beyond. Conclusion CPCRN activities have increased the ability of community organizations to compete for external funds to support implementation, increased the use of evidence in real-world settings, and promoted the broad-scale implementation of cancer control interventions across more than eight states. Lessons from this narrative review highlight the value of long-term thematic networks and provide useful guidance to other research networks and future capacity-building efforts.

Fruit juice and childhood obesity: a review of epidemiologic studies - Junichi R. Sakaki; Nancy R. Rodriguez; Maria-Luz Fernandez; Michael J. Puglisi; Ming-Hui Chen; Ock K. Chun (Critical Reviews in Food Science and Nutrition, 2023)

Xeno-estrogenic activity of real-life mixtures of perfluoroalkylated substances in human placenta homogenates - Maria Wielsøe; Jose-Manuel Molina-Molina; Andrea Rodríguez-Carrillo; Vicente Mustieles; Nicolas Olea; Mariana F. Fernandez; Eva Cecilie Bonefeld-Jørgensen (Reproductive Toxicology, 2023)

Immobilisation of contaminants by ‘green’-synthesized magnetite as a remediation approach to the phosphogypsum waste leachates model solution - Evgenia-Maria Papaslioti; Philippe Le Bouteiller; Hugo Carreira; Jean-Marc Greneche; Alejandro Fernandez-Martinez; Laurent Charlet (Journal of Environmental Management, 2023)

First assessment of soil mesofauna, microbiota, and humic substances associations in a minesoil revegetated with four grasses in Brazil: An 18-year field study - Maria Bertaso de Garcia Fernandez; Otávio dos Anjos Leal; Adão Pagani Júnior; Lívia de Oliveira Islabão; Luisa Menezes Silveira; Hullifas Lopes Nogueira; José Vitor Peroba Rocha; Beatriz Bruno Nascimento; Nathalia Lopes de Oliveira; Mauricio da Silva de Oliveira; Pablo Miguel; Luiz Fernando Spinelli Pinto; et al. (European Journal of Soil Biology, 2023)

Clinical outcomes of long-term corneas preserved frozen in Eusol-C used in emergency tectonic grafts - Barbara Burgos-Blasco; Beatriz Vidal-Villegas; Isabel Collado-Vincueria; Ana Maria Soria-García; Ricardo Cuiña-Sardiña; Rosalía Mendez-Fernandez; David Diaz-Valle; Mayte Ariño-Gutierez (Cell and Tissue Banking, 2023)

PFASs: What can we learn from the European Human Biomonitoring Initiative HBM4EU - Maria Uhl; Greet Schoeters; Eva Govarts; Wieneke Bil; Tony Fletcher; Line Småstuen Haug; Ron Hoogenboom; Claudia Gundacker; Xenia Trier; Mariana F. Fernandez; Argelia Castaño Calvo; Marta Esteban López; et al. (International Journal of Hygiene and Environmental Health, 2023)

Mixing methods for solid state electrodes: Techniques, fundamentals, recent advances, and perspectives - Leire Fernandez-Diaz; Julen Castillo; Elene Sasieta-Barrutia; Maria Arnaiz; Marta Cabello; Xabier Judez; Alexandre Terry; Laida Otaegui; Maria C. Morant-Miñana; Aitor Villaverde (Chemical Engineering Journal, 2023)

Enhancing maize grain dry-down predictive models - Yésica D. Chazarreta; Ana J.P. Carcedo; Santiago Alvarez Prado; Ignacio Massigoge; Juan I. Amas; Javier A. Fernandez; Ignacio A. Ciampitti; Maria E. Otegui (Agricultural and Forest Meteorology, 2023)

Risk reductions during pyrene biotransformation and mobilization in a model plant-bacteria-biochar system - José Carlos Castilla-Alcantara; Rosa Posada-Baquero; Maria Balseiro-Romero; Carmen Fernández-López; José Luis García; Alicia Fernandez-Vazquez; John R. Parsons; Manuel Cantos; Jose Julio Ortega-Calvo (Science of The Total Environment, 2023)

Cadmium-promoted thyroid hormones disruption mediates ROS, inflammation, Aβ and Tau proteins production, gliosis, spongiosis and neurodegeneration in rat basal forebrain - Emma Sola; Paula Moyano; Andrea Flores; José Manuel García; Jimena García; María José Anadon; María Teresa Frejo; Adela Pelayo; Maria de la Cabeza Fernandez; Javier del Pino (Chemico-Biological Interactions, 2023)

Norfloxacin prophylaxis effect on multidrug resistance in patients with cirrhosis and bacterial infections - Sebastián Marciano; Maria N. Gutierrez-Acevedo; Sabrina Barbero; Lorena del C. Notari; Marina Agozino; Jose L. Fernandez; Maria M. Anders; Nadia Grigera; Florencia Antinucci; Orlando F. Orozco Ganem; Maria D. Murga; Daniela Perez; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Implementing New Approach Methodologies (NAMs) in food safety assessments: Strategic objectives and actions taken by the European Food Safety Authority - Irene Cattaneo; Maria Chiara Astuto; Marco Binaglia; Yann Devos; Jean Lou C.M. Dorne; Ana Fernandez Agudo; Antonio Fernandez Dumont; Pilar Garcia-Vello; George E.N. Kass; Anna Lanzoni; A.K. Djien Liem; Martina Panzarea; et al. (Trends in Food Science & Technology, 2023)

Physical restoration of a minesoil after 10.6 years of revegetation - Pablo Miguel; Lizete Stumpf; Luiz Fernando Spinelli Pinto; Eloy Antonio Pauletto; Mateus Fonseca Rodrigues; Lucas Silva Barboza; Jéferson Diego Leidemer; Thábata Barbosa Duarte; Marília Alves Brito Pinto; Maria Bertaso de Garcia Fernandez; Livia Oliveira Islabão; Luisa Menezes da Silveira; et al. (Soil and Tillage Research, 2023)

Flooding affects plant–plant interactions in tree seedlings from fertile Amazonian floodplains, Brazil - Naara Ferreira da Silva; Pia Parolin; Maria Teresa Fernandez Piedade; Aline Lopes (Hydrobiologia, 2023)

Species movements within biogeographic regions: exploring the distribution of transplanted mollusc species in South America - Gustavo Darrigran; Ignacio Agudo-Padrón; Pedro Baez; Carlos Belz; Franz Cardoso; Gonzalo A. Collado; Modesto Correoso; María Gabriela Cuezzo; Cristina Damborenea; Alejandra A. Fabres; Monica A. Fernandez; Suzete R. Gomes; et al. (Biological Invasions, 2023)

Are birds more afraid in urban parks or cemeteries? A Latin American study contrasts with results from Europe - Federico Morelli; Lucas M. Leveau; Peter Mikula; Ian MacGregor-Fors; M. Lucia Bocelli; Sergio Gabriel Quesada-Acuña; César González-Lagos; Pablo Gutiérrez-Tapia; Gabriela Franzoi Dri; Carlos A. Delgado-V.; Alvaro Garitano Zavala; Jackeline Campos; et al. (Science of The Total Environment, 2023)

Biological quality and organic matter dynamics in minesoil at 18 years reclamation with perennial grasses - Maria Bertaso De Garcia Fernandez; Lizete Stumpf; Pablo Miguel; Luiz Fernando Spinelli Pinto; Filipe Selau Carlos; Ryan Noremberg Schubert; Adão Pagani Junior; Eliana Aparecida Cadona; Juliana Maciel Bicca (Ecological Engineering, 2023)

Digital placemaking, health & wellbeing and nature-based solutions: A systematic review and practice model - Maria J. Fernandez de Osso Fuentes; Brendan J. Keegan; Marc V. Jones; Tadhg MacIntyre (Urban Forestry & Urban Greening, 2023)

Assessment of the bioaccessibility of PAHs and other hazardous compounds present in recycled tire rubber employed in synthetic football fields - Daniel Armada; Antia Martinez-Fernandez; Maria Celeiro; Thierry Dagnac; Maria Llompart (Science of The Total Environment, 2023)

Continuous production of honey oligosaccharides in packed-bed reactors with immobilized α-glucosidase from Metschnikowia reukaufii - Martin Garcia-Gonzalez; Egle Narmontaite; Fadia V. Cervantes; Francisco J. Plou; Lorena Betancor; Maria Fernandez-Lobato (Biocatalysis and Agricultural Biotechnology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Soil moisture estimates over sporadically flooded farmlands: synergies and biases of remote sensing and in situ sources - Lucía M. Cappelletti; Anna A. Sörensson; Mercedes Salvia; Romina C. Ruscica; Pablo Spennemann; Maria E. Fernandez-Long; Esteban Jobbágy (International Journal of Remote Sensing, 2022)

Can Organic P Inputs Alleviate P Limitation Effects on Nutrient Uptake and Biological N2-Fixing Capacity of Hairy Vetch (Vicia villosa)? - Daniel Said-Pullicino; Rodolfo Lizcano Toledo; Cristina Lerda; Maria Martin; Flavio Fornasier; Emilia Fernandez-Ondoño; Luisella Celi (Journal of Soil Science and Plant Nutrition, 2022)
Phosphorus (P) is a limiting nutrient in many agroecosystems and, apart from affecting plant growth, can also limit biological N 2 fixation (BNF) by leguminous plants. Thus, increasing P supply can have a positive effect on BNF particularly in P-deficient soils. Here, we provide new insights into the response of hairy vetch ( Vicia villosa ), widely adopted as a legume cover crop, to P limitations, by comparing the effects of inorganic (Pi) and organic (Po) P supply on plant growth and BNF capacity. This was achieved by means of a greenhouse experiment in which rhizobia-inoculated hairy vetch was grown in a P-limited agricultural soil and changes in plant growth, nitrogen (N) and P uptake, BNF capacity, and soil phosphatases activities were evaluated as a function of Pi and Po inputs, in the form of orthophosphate or phytic acid, respectively. When compared to P-deficient conditions where BNF was primarily limited by plant growth rather than directly due to the high P costs of symbiotic N fixation, Pi addition substantially enhanced plant growth (threefold), nodule formation (16-fold), P acquisition (sixfold), and BNF efficiency (sevenfold). In contrast, even with the addition of the highest dose of Po, the increase in plant growth, nodule formation, P acquisition, and BNF capacity (1.7, 3.5, 2.4 and 2.1-fold, respectively) was much less expressed, indicating that hairy vetch could only minimally access Po sources over the growth period in order to alleviate the P limitation effect on N 2 fixation in under P-deficient conditions. These findings suggest that hairy vetch will not be able to provide sufficient BNF for improving soil N inputs in low-fertility cropping systems that rely on organic inputs.

Mapping the spatial variability of rainfall from a physiographic-based multilinear regression: model development and application to the Southwestern Iberian Peninsula - Verónica Ruiz-Ortiz; Jorge M. G. P. Isidoro; Helena Maria Fernandez; Fernando M. Granja-Martins; Santiago García-López (Environmental Monitoring and Assessment, 2022)

Advancing fishery-independent stock assessments for the Norway lobster (Nephrops norvegicus) with new monitoring technologies - Jacopo Aguzzi; Damianos Chatzievangelou; Nathan J. Robinson; Nixon Bahamon; Alan Berry; Marc Carreras; Joan Batista Company; Corrado Costa; Joaquin del Rio Fernandez; Ahmad Falahzadeh; Spyros Fifas; Sascha Flögel; et al. (Frontiers in Marine Science, 2022)
The Norway lobster, Nephrops norvegicus , supports a key European fishery. Stock assessments for this species are mostly based on trawling and UnderWater TeleVision (UWTV) surveys. However, N. norvegicus are burrowing organisms and these survey methods are unable to sample or observe individuals in their burrows. To account for this, UWTV surveys generally assume that “1 burrow system = 1 animal”, due to the territorial behavior of N. norvegicus . Nevertheless, this assumption still requires in-situ validation. Here, we outline how to improve the accuracy of current stock assessments for N. norvegicus with novel ecological monitoring technologies, including: robotic fixed and mobile camera-platforms, telemetry, environmental DNA (eDNA), and Artificial Intelligence (AI). First, we outline the present status and threat for overexploitation in N. norvegicus stocks. Then, we discuss how the burrowing behavior of N. norvegicus biases current stock assessment methods. We propose that state-of-the-art stationary and mobile robotic platforms endowed with innovative sensors and complemented with AI tools could be used to count both animals and burrows systems in-situ , as well as to provide key insights into burrowing behavior. Next, we illustrate how multiparametric monitoring can be incorporated into assessments of physiology and burrowing behavior. Finally, we develop a flowchart for the appropriate treatment of multiparametric biological and environmental data required to improve current stock assessment methods.

Oral Administration of Probiotics (Bacillus subtilis and Lactobacillus plantarum) in Nile Tilapia (Oreochromis niloticus) Vaccinated and Challenged with Streptococcus agalactiae - Mateus Cardoso Guimarães; Isabel M. Cerezo; Miguel Frederico Fernandez-Alarcon; Mariene Miyoko Natori; Luciana Yuri Sato; Camila A. T. Kato; Miguel Angel Moriñigo; Silvana Tapia-Paniagua; Danielle de Carla Dias; Carlos Massatoshi Ishikawa; Maria José T. Ranzani-Paiva; Luara Lucena Cassiano; et al. (Fishes, 2022)
Streptococcus agalactiae is an important bacterial pathogen in intensive Nile tilapia production, causing high mortality rates and great economic losses. This work aimed to evaluate the Nile tilapia vaccination against S. agalactiae and fed with ration containing probiotic AQUA PHOTO® composed of Bacillus subtilis and Lactobacillus plantarum, on the immune response action and gut microbiota. The experimental design was completely randomized with five treatments (CON = control; ADJ = adjuvant; PRO = probiotic; VAC = vaccine; PRO + VAC = probiotic + vaccine) and five replicates. The vaccine (bacterin + adjuvant) was injected after 21 days (21d) of probiotic feeding and the vaccine was booster 14 days post-vaccination (35d). After 14 days of the booster (49d), the fish were challenged with S. agalactiae and observed for more than 14 days, completing 63 days. The immunized group showed a better survival rate (CON 40%; ADJ 57%; PRO 67%; VAC 87%; PRO + VAC 97%). The treatments VAC and PRO + VAC, after booster produced higher levels of IgM antibodies compared with the control from the same time. The combination of probiotic and vaccination provided better protection against S. agalactiae infection, directly affecting the gut microbiological profile. These results indicated the contribution of probiotic to the adaptive immune response through the modulation of the intestinal microbiota, improving the effect of the vaccination. In conclusion, AQUA PHOTO®, composed of B. subtilis and L. plantarum, orally administered to Nile tilapia vaccinated against and challenged with S. agalactiae increases protection from infection and modifies the intestinal microbiota profile of the host, promoting the microbiota balance and improving adaptive immune response.

Water chemistry of rivers and streams from the Jaú and Uatumã basins in central Brazilian Amazon - Eduardo Antonio Ríos-Villamizar; Aline Lopes; Maria do Socorro Rocha da Silva; Nilyan Adria Santarém dos Santos; Regison Oliveira; Robson M. Calazães; Maria Teresa Fernandez Piedade; Jochen Schöngart; Bruce R. Forsberg; Florian Wittmann; Wolfgang J. Junk (Sustainable Water Resources Management, 2022)

Comparison of two-dimensional and three-dimensional U-Net architectures for segmentation of adipose tissue in cardiac magnetic resonance images - Michaela Kulasekara; Vu Quang Dinh; Maria Fernandez-del-Valle; Jon D. Klingensmith (Medical & Biological Engineering & Computing, 2022)

Insulin-like growth factor I sensitization rejuvenates sleep patterns in old mice - Jonathan A. Zegarra-Valdivia; Jansen Fernandes; Maria Estrella Fernandez de Sevilla; Angel Trueba-Saiz; Jaime Pignatelli; Kentaro Suda; Laura Martinez-Rachadell; Ana Maria Fernandez; Julio Esparza; Miguel Vega; Angel Nuñez; Ignacio Torres Aleman (GeroScience, 2022)

An Exploratory Survey on the Care for Ataxic Patients in the American Continents and the Caribbean - Laura Bannach Jardim; Ali Hasan; Sheng-han Kuo; Jonathan Javier Magaña; Marcondes França; Wilson Marques; Claudia Camejo; Luiz Carlos Santana-da-Silva; Emília Embiruçu Leão; Gisele Espíndola; Francisca Canals; Marcelo Miranda; et al. (The Cerebellum, 2022)

Cytotoxicity and anti-inflammatory activities of Gallesia integrifolia (Phytolaccaceae) fruit essential oil - Wanessa de Campos Bortolucci; Keila Fernanda Raimundo; Carla Maria Mariano Fernandez; Ricardo C. Calhelha; Isabel C. F. R. Ferreira; Lillian Barros; José Eduardo Gonçalves; Giani Andrea Linde; Nelson Barros Colauto; Zilda Cristiani Gazim (Natural Product Research, 2022)

Legume Tree Dominance in Central Amazonian Floodplain Forests - Yuri Oliveira Feitosa; Maria Teresa Fernandez Piedade; Florian Wittmann; Adriano Costa Quaresma; Angélica Faria de Resende; Rafael Leandro de Assis; Jochen Schöngart (Wetlands, 2022)

Muscular carnosine is a marker for cardiorespiratory fitness and cardiometabolic risk factors in men with type 1 diabetes - Laura Brugnara; Ana Isabel García; Serafín Murillo; Josep Ribalta; Guerau Fernandez; Susanna Marquez; Miguel Angel Rodriguez; Maria Vinaixa; Núria Amigó; Xavier Correig; Susana Kalko; Jaume Pomes; et al. (European Journal of Applied Physiology, 2022)

Genetic characterization of Chikungunya virus circulating in individuals from Paraná, Brazil - Deborah de Castro Moreira; Francisco Ferreira Duarte Junior; José Renato Pattaro Júnior; Fernando Américo Jorge; Fabiana dos Santos Rando; Mateus Vaillant Thomazella; Mayra Marinho Presibella; Irina Nastassja Riediger; Maria Aparecida Fernandez; Dennis Armando Bertolini (Brazilian Journal of Microbiology, 2022)

Chemistry of surface water, precipitation, throughfall, leaves, sediment, soil, and air near a gold mining region in P eru - Jacqueline R. Gerson; Natalie Szponar; Arianna Agostini; Rand Alotaibi; Bridget Bergquist; Arabella Chen; Luis E. Fernandez; Kelsey N. Lansdale; Anne H. Lee; Maria F. Machicao; Melissa J. Marchese; Simon N. Topp; et al. (Ecology, 2022)
Artisanal and small‐scale gold mining (ASGM) is the primary global source of anthropogenic mercury (Hg) emissions and a large source of landscape change. ASGM occurs throughout the world, including in the Peruvian Amazon. This data set contains measurements of surface water, precipitation, throughfall, leaves, sediment, soil, and air samples from across the Madre de Dios region of Peru, in locations near and remote from ASGM. These data were collected to determine the fate and transport of Hg across the landscape. Samples were collected in 2018 and 2019. Data predominantly included total Hg and methyl Hg concentrations in surface water, precipitation, throughfall, leaves, sediment, soil, and air. Additional water and soil parameters were also measured to better characterize their chemistry. There are no copyright restrictions; please cite this data paper when the data are used in publication.

Knowledge, Attitudes, Willingness to Pay, and Patient Preferences About Genetic Testing and Subsequent Risk Management for Cancer Prevention - Fangjian Guo; Jacqueline M. Hirth; Erika L. Fuchs; Leslie E. Cofie; Veronica Brown; Yong-Fang Kuo; Maria E. Fernandez; Abbey B. Berenson (Journal of Cancer Education, 2022)

Socio‐ecological drivers of multiple zoonotic hazards in highly urbanized cities - Matthew A. Combs; Pallavi A. Kache; Meredith C. VanAcker; Nichar Gregory; Laura D. Plimpton; Danielle M. Tufts; Maria P. Fernandez; Maria A. Diuk‐Wasser (Global Change Biology, 2022)
The ongoing COVID‐19 pandemic is a stark reminder of the devastating consequences of pathogen spillover from wildlife to human hosts, particularly in densely populated urban centers. Prevention of future zoonotic disease is contingent on informed surveillance for known and novel threats across diverse human–wildlife interfaces. Cities are a key venue for potential spillover events because of the presence of zoonotic pathogens transmitted by hosts and vectors living in close proximity to dense human settlements. Effectively identifying and managing zoonotic hazards requires understanding the socio‐ecological processes driving hazard distribution and pathogen prevalence in dynamic and heterogeneous urban landscapes. Despite increasing awareness of the human health impacts of zoonotic hazards, the integration of an eco‐epidemiological perspective into public health management plans remains limited. Here we discuss how landscape patterns, abiotic conditions, and biotic interactions influence zoonotic hazards across highly urbanized cities (HUCs) in temperate climates to promote their efficient and effective management by a multi‐sectoral coalition of public health stakeholders. We describe how to interpret both direct and indirect ecological processes, incorporate spatial scale, and evaluate networks of connectivity specific to different zoonotic hazards to promote biologically‐informed and targeted decision‐making. Using New York City, USA as a case study, we identify major zoonotic threats, apply knowledge of relevant ecological factors, and highlight opportunities and challenges for research and intervention. We aim to broaden the toolbox of urban public health stakeholders by providing ecologically‐informed, practical guidance for the evaluation and management of zoonotic hazards.

Larvicidal activity of Brunfelsia uniflora extracts on Aedes aegypti larvae - Elaine Yae Yamashita Sugauara; ElisângelaYumi Sugauara; Rosângela Rumi Sugauara; Wanessa de Campos Bortolucci; Carla Maria Mariano Fernandez; José Eduardo Gonçalves; Nelson Barros Colauto; Zilda Cristiani Gazim; Giani Andrea Linde (Natural Product Research, 2022)

Framing Cutting-Edge Integrative Deep-Sea Biodiversity Monitoring via Environmental DNA and Optoacoustic Augmented Infrastructures - Sergio Stefanni; Luca Mirimin; David Stanković; Damianos Chatzievangelou; Lucia Bongiorni; Simone Marini; Maria Vittoria Modica; Elisabetta Manea; Federico Bonofiglio; Joaquin del Rio Fernandez; Neven Cukrov; Ana Gavrilović; et al. (Frontiers in Marine Science, 2022)
Deep-sea ecosystems are reservoirs of biodiversity that are largely unexplored, but their exploration and biodiscovery are becoming a reality thanks to biotechnological advances (e.g., omics technologies) and their integration in an expanding network of marine infrastructures for the exploration of the seas, such as cabled observatories. While still in its infancy, the application of environmental DNA (eDNA) metabarcoding approaches is revolutionizing marine biodiversity monitoring capability. Indeed, the analysis of eDNA in conjunction with the collection of multidisciplinary optoacoustic and environmental data, can provide a more comprehensive monitoring of deep-sea biodiversity. Here, we describe the potential for acquiring eDNA as a core component for the expanding ecological monitoring capabilities through cabled observatories and their docked Internet Operated Vehicles (IOVs), such as crawlers. Furthermore, we provide a critical overview of four areas of development: (i) Integrating eDNA with optoacoustic imaging; (ii) Development of eDNA repositories and cross-linking with other biodiversity databases; (iii) Artificial Intelligence for eDNA analyses and integration with imaging data; and (iv) Benefits of eDNA augmented observatories for the conservation and sustainable management of deep-sea biodiversity. Finally, we discuss the technical limitations and recommendations for future eDNA monitoring of the deep-sea. It is hoped that this review will frame the future direction of an exciting journey of biodiscovery in remote and yet vulnerable areas of our planet, with the overall aim to understand deep-sea biodiversity and hence manage and protect vital marine resources.

Chemical composition of Tradescantia pallida (Rose) D.R. Hunt var. purpurea Boom (Commelinaceae) essential oil - Renato Fernando Menegazzo; Wanessa de Campos Bortolucci; Herika Line Marko de Oliveira; André Werlang Menegazzo; José Eduardo Gonçalves; Carla Maria Mariano Fernandez; Zilda Cristiani Gazim; Ana Daniela Lopes (Natural Product Research, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Campomanesia xanthocarpa (Mart.) O. Berg essential oil induces antileishmanial activity and remodeling of the cytoplasm organelles - Fabiana Borges Padilha Ferreira; Áquila Carolina Fernandes Herculano Ramos-Milaré; José Eduardo Gonçalves; Danielle Lazarin-Bidóia; Celso Vataru Nakamura; Rosangela Rumi Sugauara; Carla Maria Mariano Fernandez; Zilda Cristiani Gazim; Izabel Galhardo Demarchi; Thaís Gomes Verzignassi Silveira; Maria Valdrinez Campana Lonardoni (Natural Product Research, 2021)

Minimum temperature and evapotranspiration in Central Amazonian floodplains limit tree growth of Nectandra amazonum (Lauraceae) - Janaína Quixabeira Gonçalves; Flávia Machado Durgante; Florian Wittmann; Maria Teresa Fernandez Piedade; Daigard Ricardo Ortega Rodriguez; Mário Tomazello-Filho; Pia Parolin; Jochen Schöngart (Trees, 2021)

Phenological behavior and floral visitors of Pentaclethra macroloba, a hyperdominant tree in the Brazilian Amazon River estuary - Adelson Rocha Dantas; Marcelino Carneiro Guedes; Ana Cláudia Lira-Guedes; Maria Teresa Fernandez Piedade (Trees, 2021)

In vitro conservation of centennial Austrian Cornelian cherry accessions - Margit Laimer; Maria Zeiser; Veronika Hanzer; E. G. Borroto Fernandez (Plant Biotechnology Reports, 2021)
Cornelian cherry ( Cornus mas ) appears in a list of fruit and nut species growing in Europe considered neglected and underused economically. Although C. mas has a long-standing traditional medicinal use, only in recent years interest in products and food made from Cornelian cherries, said to have health-promoting effects, increased. This in turn raises the demand for improved planting material. In the Pielach Valley Region, Lower Austria, hundreds of centenary specimens of Cornus mas , but even a few millennial plants can still be encountered. The occurrence of these plants requested an active intervention to genetically characterize and preserve this valuable biodiversity, particularly in the light of changing environmental conditions. Efforts for the establishment of an in vitro collection of this valuable germplasm of centenary cornelian cherries yielded 193 mericlones initiated from single node explants from 41 selected plants. The selected donor plants were grouped by estimated age ranging from 10 years, > 50 years, > 100 years, > 200 years, > 400 years and 1000 years. The final goal of our efforts is to preserve these genetic resources, also checked for genetic and phytosanitary quality, for future generations and to use the superior clones for further breeding programs.

Edaphic characteristics drive functional traits distribution in Amazonian floodplain forests - Gisele Biem Mori; Lourens Poorter; Juliana Schietti; Maria Teresa Fernandez Piedade (Plant Ecology, 2021)

Genomic Analysis of two NDM-1 Providencia stuartii Strains Recovered from a Single Patient - Amparo Hoard; Sabrina Montaña; Alessandro Moriano; Jennifer S. Fernandez; German M. Traglia; Cecilia Quiroga; Agustina Franchi; Emilia Cohen; Cecilia Corigliano; Marisa Almuzara; Maria Soledad Ramirez (Current Microbiology, 2020)

Effect of agitation speed and aeration rate on fructosyltransferase production of Aspergillus oryzae IPT-301 in stirred tank bioreactor - Alfredo Eduardo Maiorano; Elda Sabino da Silva; Rafael Firmani Perna; Cristiane Angélica Ottoni; Rosane Aparecida Moniz Piccoli; Rubén Cuervo Fernandez; Beatriz Guilarte Maresma; Maria Filomena de Andrade Rodrigues (Biotechnology Letters, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

New insights on the classification of major Amazonian river water types - Eduardo Antonio Ríos-Villamizar; J. Marion Adeney; Maria Teresa Fernandez Piedade; Wolfgang Johannes Junk (Sustainable Water Resources Management, 2020)

Chemical composition, antileishmanial and antioxidant activity of Eugenia moraviana (Myrtaceae) fruit extract - Fabiana Borges Padilha Ferreira; Áquila Carolina Fernandes Herculano Ramos-Milaré; Márcia Regina Pereira Cabral; Danielle Lazarin-Bidóia; Celso Vataru Nakamura; Maria Helena Sarragiotto; Wanessa de Campos Bortolucci; Carla Maria Mariano Fernandez; Zilda Cristiani Gazim; Izabel Galhardo Demarchi; Thaís Gomes Verzignassi Silveira; Maria Valdrinez Campana Lonardoni (Medicinal Chemistry Research, 2020)

Evolutionarily conserved plant genes responsive to root-knot nematodes identified by comparative genomics - Ana Paula Zotta Mota; Diana Fernandez; Fabricio B. M. Arraes; Anne-Sophie Petitot; Bruno Paes de Melo; Maria E. Lisei de Sa; Priscila Grynberg; Mario A. Passos Saraiva; Patricia Messenberg Guimaraes; Ana Cristina Miranda Brasileiro; Erika Valeria Saliba Albuquerque; Etienne G. J. Danchin; et al. (Molecular Genetics and Genomics, 2020)

Antioxidant activity of α and β -amyrin isolated from Myrcianthes pungens leaves - Bruna Karen Cardoso; Herika Line Marko de Oliveira; Ulisses Zonta Melo; Carla Maria Mariano Fernandez; Caio Franco de Araújo Almeida Campo; José Eduardo Gonçalves; Antônio Laverde Jr; Mariza Barion Romagnolo; Giani Andrea Linde; Zilda Cristiani Gazim (Natural Product Research, 2020)

Founder Effects of Spinocerebellar Ataxias in the American Continents and the Caribbean - Roberto Rodríguez-Labrada; Ana Carolina Martins; Jonathan J. Magaña; Yaimeé Vazquez-Mojena; Jacqueline Medrano-Montero; Juan Fernandez-Ruíz; Bulmaro Cisneros; Helio Teive; Karen N. McFarland; Maria Luiza Saraiva-Pereira; César M. Cerecedo-Zapata; Christopher M. Gomez; et al. (The Cerebellum, 2020)

Interactions between putatively endophytic bacteria and tall fescue (Festuca arundinacea): plant growth promotion and colonization in host and non-host cultivars - Patricia Vaz Jauri; Cecilia Taulé; Maria Cecilia de los Santos; Belén Fernandez; Andrés Di Paolo; José Sotelo; Federico Battistoni (Plant and Soil, 2020)

Leaf consumption by invertebrate aquatic shredders in the Amazon: effects of climate change and microbial conditioning - Renato Tavares Martins; José Francisco Gonçalves; Claudimir Menezes Campos; Aline Lopes; Maria Teresa Fernandez Piedade; Neusa Hamada (Limnology, 2020)

Toward a Comprehensive and Integrated Strategy of the European Marine Research Infrastructures for Ocean Observations - Juan Jose Dañobeitia; Sylvie Pouliquen; Truls Johannessen; Alberto Basset; Mathilde Cannat; Benjamin Gerrit Pfeil; Maria Incoronata Fredella; Paola Materia; Claire Gourcuff; Giuseppe Magnifico; Eric Delory; Joaquin del Rio Fernandez; et al. (Frontiers in Marine Science, 2020)

Essential oil and fractions isolated of Laurel to control adults and larvae of cattle ticks - Carla Maria Mariano Fernandez; Maurício Ferreira da Rosa; Ana Claudia Aparecida Mariano Fernandez; Wanessa de Campos Bortolucci; Fabiana Borges Padilha Ferreira; Giani Andrea Linde; Nelson Barros Colauto; Márcia Regina Simões; Viviane da Silva Lobo; Zilda Cristiani Gazim (Natural Product Research, 2020)

Serum matrix metalloproteinase-9 in children exposed to arsenic from playground dust at elementary schools in Hermosillo, Sonora, Mexico - Leticia García-Rico; Diana Meza-Figueroa; Paloma I. Beamer; Jefferey L. Burgess; Mary K. O’Rourke; Clark R. Lantz; Melissa Furlong; Marco Martinez-Cinco; Iram Mondaca-Fernandez; Jose J. Balderas-Cortes; Maria M. Meza-Montenegro (Environmental Geochemistry and Health, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Educating Hispanics About Clinical Trials and Biobanking - M. Lizette Rangel; Natalia I. Heredia; Belinda Reininger; Lorna McNeill; Maria E. Fernandez (Journal of Cancer Education, 2019)

Rice susceptibility to root-knot nematodes is enhanced by the Meloidogyne incognita MSP18 effector gene - Maíra Grossi-de-Sa; Anne-Sophie Petitot; Deisy A. Xavier; Maria Eugênia L. Sá; Itamara Mezzalira; Magda A. Beneventi; Natalia F. Martins; Hugues K. Baimey; Erika V. S. Albuquerque; Maria F. Grossi-de-Sa; Diana Fernandez (Planta, 2019)

Biophysical characterization and molecular phylogeny of human KIN protein - José Renato Pattaro Júnior; Ícaro Putinhon Caruso; Quirino Alves de Lima Neto; Francisco Ferreira Duarte Junior; Fabiana dos Santos Rando; Edileusa Cristina Marques Gerhardt; Maria Aparecida Fernandez; Flávio Augusto Vicente Seixas (European Biophysics Journal, 2019)

Comments on “Use of Rh (III)-Heteropolymolybdate as Potential Catalysts for the Removal of Nitrates in Human Drinking Water: Synthesis, Characterisation and Catalytic Performance” by María A. Jaworski et al. (Water Air Soil Pollut (2018) 229: 309) - Francisco Ruiz-Bevia; Maria J. Fernandez-Torres (Water, Air, & Soil Pollution, 2019)

Effect of Host Human Products on Natural Transformation in Acinetobacter baumannii - Brettni Quinn; German M. Traglia; Meaghan Nguyen; Jasmine Martinez; Christine Liu; Jennifer S. Fernandez; Maria Soledad Ramirez (Current Microbiology, 2019)

A Study on Acinetobacter baumannii and Staphylococcus aureus Strains Recovered from the Same Infection Site of a Diabetic Patient - Nancy Castellanos; Jun Nakanouchi; Dennis Irfan Yüzen; Sammie Fung; Jennifer S. Fernandez; Claudia Barberis; Lorena Tuchscherr; Maria Soledad Ramirez (Current Microbiology, 2019)

Increased serum ferritin and interleukin-18 levels in children with dengue - Nereida Valero; Jesus Mosquera; Mariana Torres; Anyelo Duran; Maria Velastegui; Javier Reyes; Miriam Fernandez; Gerardo Fernandez; Teresa Veliz (Brazilian Journal of Microbiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

In vitro antioxidant potential and in vivo effects of Schinus terebinthifolia Raddi leaf extract in diabetic rats and determination of chemical composition by HPLC-ESI-MS/MS - Camila Cristina Iwanaga; Lilian dos Anjos Oliveira Ferreira; Karine Zanoli Bernuci; Carla Maria Mariano Fernandez; Fabiana Brusco Lorenzetti; Camila Caviquioli Sehaber; Flávia Cristina Vieira Frez; Sara Santos Bernardes; Gean Pier Panizzon; Giani Andrea Linde; Maria do Carmo Vieira; Jacqueline Nelisis Zanoni; et al. (Natural Product Research, 2019)

Heightened nest loss in tropical forest fragments despite higher predator load in core forest - Christopher M. Fernandez; Maria D. Vera Alvarez; Michael V. Cove (Tropical Ecology, 2019)

A database approach for materials selection for hydrogen storage in aerospace technology - Carla Maria Coppola; Iogann Tolbatov; Ionut Claudiu Tranca; Cecilia Coletti; Alessandro Marrone; Loriano Storchi; Pietro Di Profio; Nazzareno Re; Mher V. Kazandjian; Antonello Pellecchia; Savino Longo; Silvia Gaastra-Nedea; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2019)

Does water type influence diet composition in Amazonian manatee (Trichechus inunguis)? A case study comparing black and clearwater rivers - Luciana Carvalho Crema; Vera Maria Ferreira da Silva; Silvina Botta; Susan Trumbore; Maria Teresa Fernandez Piedade (Hydrobiologia, 2019)

Towards the valorization of the invasive seaweeds Caulerpa cylindracea and Asparagopsis taxiformis in the Mediterranean Sea: applications for in vitro plant regeneration and crop protection - Nuria Alburquerque; Lydia Faize; Mohamed Faize; Maria Dolores Nortes; Jaime Bernardeau; Juan Manuel Ruiz Fernandez; Lorenzo Burgos (Journal of Applied Phycology, 2019)

Improving engraftment of hepatocyte transplantation using alpha-1 antitrypsin as an immune modulator - Charlotte Lee; Anil Dhawan; Valeria Iansante; Celine Filippi; Ragai Mitry; Joanne Tang; Simon Walker; Raquel Fernandez DaCosta; Siddharth Sinha; Robin D. Hughes; Maria Koulmanda; Emer Fitzpatrick (Journal of Molecular Medicine, 2019)

A single-crystal neutron diffraction study of wardite, NaAl3(PO4)2(OH)4·2H2O - G. Diego Gatta; Alessandro Guastoni; Oscar Fabelo; Maria Teresa Fernandez-Diaz (Physics and Chemistry of Minerals, 2019)

Anaerobic Digestion Process for the Production of Biogas from Cassava and Sewage Treatment Plant Sludge in Brazil - Sergio Peres; Marina Rebeca Monteiro; Micheline Lima Ferreira; Adalberto Freire do Nascimento Junior; Maria de Los Angeles Perez Fernandez Palh (BioEnergy Research, 2019)

Evaluating centralized technical assistance as an implementation strategy to improve cancer prevention and control - Sarah Moreland-Russell; Prajakta Adsul; Seif Nasir; Maria E. Fernandez; Timothy J. Walker; Heather M. Brandt; Robin C. Vanderpool; Meagan Pilar; Paula Cuccaro; Wynne E. Norton; Cynthia A. Vinson; David A. Chambers; et al. (Cancer Causes & Control, 2018)

Conflicting energy policy priorities in EU energy governance - Rosa Maria Fernandez (Journal of Environmental Studies and Sciences, 2018)

Ginger rhizome enhances the anti-inflammatory and anti-nociceptive effects of paracetamol in an experimental mouse model of fibromyalgia - Sergio Montserrat-de la Paz; Maria Dolores Garcia-Gimenez; Ana Maria Quilez; Rocio De la Puerta; Angeles Fernandez-Arche (Inflammopharmacology, 2018)

Combined effect of elevated CO2 level and temperature on germination and initial growth of Montrichardia arborescens (L.) Schott (Araceae): a microcosm experiment - Aline Lopes; Aurélia Bentes Ferreira; Pauline Oliveira Pantoja; Pia Parolin; Maria Teresa Fernandez Piedade (Hydrobiologia, 2018)

Effects of resistance training on MRI-derived epicardial fat volume and arterial stiffness in women with obesity: a randomized pilot study - Maria Fernandez-del-Valle; Joaquin U. Gonzales; Shelby Kloiber; Sunanda Mitra; Jon Klingensmith; Eneko Larumbe-Zabala (European Journal of Applied Physiology, 2018)

Crystal chemistry and temperature behavior of the natural hydrous borate colemanite, a mineral commodity of boron - Paolo Lotti; G. Diego Gatta; Nicola Demitri; Giorgio Guastella; Silvia Rizzato; Marco Aldo Ortenzi; Fabrizio Magrini; Davide Comboni; Alessandro Guastoni; Maria Teresa Fernandez-Diaz (Physics and Chemistry of Minerals, 2018)

Bifidobacterium adolescentis (DSM 20083) and Lactobacillus casei (Lafti L26-DSL): Probiotics Able to Block the In Vitro Adherence of Rotavirus in MA104 Cells - Karem Prunella Fernandez-Duarte; Nury Nathalia Olaya-Galán; Sandra Patricia Salas-Cárdenas; Jazmin Lopez-Rozo; Maria Fernanda Gutierrez-Fernandez (Probiotics and Antimicrobial Proteins, 2018)

An operational-oriented approach to the assessment of low probability seismic ground motions for critical infrastructures - Mariano Garcia-Fernandez; Karen Assatourians; Maria-Jose Jimenez (Journal of Seismology, 2018)

Pediococcus acidolactici and Pediococcus pentosaceus isolated from a rainbow trout ecosystem have probiotic and ABF1 adsorbing/degrading abilities in vitro - Maria Pia Martinez; Maria Laura Gonzalez Pereyra; Gabriela Alejandra Pena; Valeria Poloni; Guillermina Fernandez Juri; Lilia Reneé Cavaglieri (Food Additives & Contaminants: Part A, 2017)

Long-Term Mangiferin Extract Treatment Improves Central Pathology and Cognitive Deficits in APP/PS1 Mice - Carmen Infante-Garcia; Juan Jose Ramos-Rodriguez; Irene Delgado-Olmos; Carlos Gamero-Carrasco; Maria Teresa Fernandez-Ponce; Lourdes Casas; Casimiro Mantell; Monica Garcia-Alloza (Molecular Neurobiology, 2017)

Ferruginous compounds in the airborne particulate matter of the metropolitan area of Belo Horizonte, Minas Gerais, Brazil - Fernanda Vasconcelos Fonseca Tavares; José Domingos Ardisson; Paulo César Horta Rodrigues; José Domingos Fabris; Luis Eugenio Fernandez-Outon; Vanusa Maria Delage Feliciano (Environmental Science and Pollution Research, 2017)

Atmospheric Deposition Effects on Plankton Communities in the Eastern Mediterranean: A Mesocosm Experimental Approach - Tatiana M. Tsagaraki; Barak Herut; Eyal Rahav; Ilana R. Berman Frank; Anastasia Tsiola; Manolis Tsapakis; Antonia Giannakourou; Alexandra Gogou; Christos Panagiotopoulos; Kalliopi Violaki; Stella Psarra; Anna Lagaria; et al. (Frontiers in Marine Science, 2017)

Submergence, seed germination, and seedling development of the Amazonian floodplain tree Pseudobombax munguba: evidence for root oxytropism - Cristiane Silva Ferreira; Maria Teresa Fernandez Piedade; Augusto Cesar Franco (Trees, 2017)

Modeling of regional- and local-scale distribution of the genus Montrichardia Crueg. (Araceae) - Aline Lopes; Florian Wittmann; Jochen Schöngart; John Ethan Householder; Maria Teresa Fernandez Piedade (Hydrobiologia, 2017)

Composition, diversity, and structure of tidal “Várzea” and “Igapó” floodplain forests in eastern Amazonia, Brazil - Marcelo de Jesus Veiga Carim; Florian Karl Wittmann; Maria Teresa Fernandez Piedade; José Renan da Silva Guimarães; Luciedi de Cássia Leôncio Tostes (Brazilian Journal of Botany, 2017)

Weather types and rainfall microstructure in Leon, Spain - Maria Fernandez‐Raga; Amaya Castro; Elena Marcos; Covadonga Palencia; Roberto Fraile (International Journal of Climatology, 2017)
Lamb's weather types classification has been used here to analyse the characteristics of raindrops in relation with the meteorological situation. A rainfall gathering campaign has been carried out in Leon [northwesterly ( NW ) Spain] over 34 months. An optical disdrometer has been used to determine drop sizes and the meteorological situations have been classified from the pressure values at surface level in 16 grid points over the study zone. The results have revealed seasonal differences in the average duration of the rain events: 40 min in winter and 12 in summer. In the study period, the rainiest weather types were the cyclonic types, and the air flows from the north and the west. The raindrop sizes follow a gamma distribution with a higher mode in the case of the weather types with air masses from the west and the southwest. The only exception lies in the purely directional weather types, where a higher mode is found in the case of rain events with eastern flows.

Response of the Calanoid Copepod Clausocalanus furcatus, to Atmospheric Deposition Events: Outcomes from a Mesocosm Study - Epaminondas D. Christou; Soultana Zervoudaki; Ma Luz Fernandez De Puelles; Maria Protopapa; Ioanna Varkitzi; Paraskevi Pitta; Tatiana M. Tsagaraki; Barak Herut (Frontiers in Marine Science, 2017)

Network meta-analysis of first- and second-generation protease inhibitors for chronic hepatitis C genotype 1: efficacy based on RVR and SVR 24 - Helena H. Borba; Astrid Wiens; Laiza M. Steimbach; Cassio M. Perlin; Fernanda S. Tonin; Maria L. A. Pedroso; Fernando Fernandez-Llimos; Roberto Pontarolo (European Journal of Clinical Pharmacology, 2017)

A robust debris-flow and GLOF risk management strategy for a data-scarce catchment in Santa Teresa, Peru - Holger Frey; Christian Huggel; Yves Bühler; Daniel Buis; Maria Dulce Burga; Walter Choquevilca; Felipe Fernandez; Javier García Hernández; Claudia Giráldez; Edwin Loarte; Paul Masias; Cesar Portocarrero; et al. (Landslides, 2016)

Genetic structure and viability selection in the golden eagle (Aquila chrysaetos), a vagile raptor with a Holarctic distribution - Jacqueline M. Doyle; Todd E. Katzner; Gary W. Roemer; James W. Cain; Brian A. Millsap; Carol L. McIntyre; Sarah A. Sonsthagen; Nadia B. Fernandez; Maria Wheeler; Zafer Bulut; Peter H. Bloom; J. Andrew DeWoody (Conservation Genetics, 2016)

Global genetic diversity of Aedes aegypti - Andrea Gloria‐Soria; Diego Ayala; Ambicadutt Bheecarry; Olger Calderon‐Arguedas; Dave D. Chadee; Marina Chiappero; Maureen Coetzee; Khouaildi Bin Elahee; Ildefonso Fernandez‐Salas; Hany A. Kamal; Basile Kamgang; Emad I. M. Khater; et al. (Molecular Ecology, 2016)
Mosquitoes, especially Aedes aegypti , are becoming important models for studying invasion biology. We characterized genetic variation at 12 microsatellite loci in 79 populations of Ae. aegypti from 30 countries in six continents, and used them to infer historical and modern patterns of invasion. Our results support the two subspecies Ae. aegypti formosus and Ae. aegypti aegypti as genetically distinct units. Ae. aegypti aegypti populations outside Africa are derived from ancestral African populations and are monophyletic. The two subspecies co‐occur in both East Africa (Kenya) and West Africa (Senegal). In rural/forest settings (Rabai District of Kenya), the two subspecies remain genetically distinct, whereas in urban settings, they introgress freely. Populations outside Africa are highly genetically structured likely due to a combination of recent founder effects, discrete discontinuous habitats and low migration rates. Ancestral populations in sub‐Saharan Africa are less genetically structured, as are the populations in Asia. Introduction of Ae. aegypti to the New World coinciding with trans‐Atlantic shipping in the 16th to 18th centuries was followed by its introduction to Asia in the late 19th century from the New World or from now extinct populations in the Mediterranean Basin. Aedes mascarensis is a genetically distinct sister species to Ae. aegypti s.l. This study provides a reference database of genetic diversity that can be used to determine the likely origin of new introductions that occur regularly for this invasive species. The genetic uniqueness of many populations and regions has important implications for attempts to control Ae. aegypti , especially for the methods using genetic modification of populations.

Quantitative trait loci for Fusarium and Gibberella ear rot resistance in Argentinian maize germplasm - Gerardo M. Giomi; Enrique D. Kreff; Juliana Iglesias; Carolina M. Fauguel; Mariana Fernandez; Maria Silvina Oviedo; Daniel A. Presello (Euphytica, 2016)

Path effects and local elastic site amplification: two case studies on Mt Etna (Italy) and Vega Baja (SE Spain) - Luciano Scarfi; Horst Langer; Mariano Garcia-Fernandez; Maria-Jose Jimenez (Bulletin of Earthquake Engineering, 2016)

The size distribution of organic carbon in headwater streams in the Amazon basin - Joana D’Arc de Paula; Flávio Jesus Luizão; Maria Teresa Fernandez Piedade (Environmental Science and Pollution Research, 2016)

Morphological and physiological traits of aquatic macrophytes respond to water chemistry in the Amazon Basin: an example of the genus Montrichardia Crueg (Araceae) - Aline Lopes; Pia Parolin; Maria Teresa Fernandez Piedade (Hydrobiologia, 2016)

Temperature and fish community in the Cantabrian Sea - Punzon Merino Antonio; Lopez Lopez Lucia; González Irusta Jose Manuel; Preciado Ramirez Izaskun; Hidalgo Manuel; Serrrano Alberto; Tel Elena; Ruiz Susana; Fernandez Zapico Olaya; Blanco Giner Maria Angeles (Frontiers in Marine Science, 2016)

Seed-Specific Stable Expression of the α-AI1 Inhibitor in Coffee Grains and the In Vivo Implications for the Development of the Coffee Berry Borer - Érika V. S. Albuquerque; Caroline A. Bezerra; Juan V. Romero; Jorge W. A. Valencia; Arnubio Valencia-Jiménez; Lucas M. Pimenta; Aulus E. A. D. Barbosa; Maria C. M. Silva; Ana M. Meneguim; Maria Eugênia L. Sá; Gilbert Engler; Janice de Almeida-Engler; et al. (Tropical Plant Biology, 2015)

In‐planta sporulation phenotype: a major life history trait to understand the evolution of A lnus ‐infective F rankia strains - Adrien C. Pozzi; Hector H. Bautista‐Guerrero; Imen Nouioui; Laëtitia Cotin‐Galvan; Régis Pepin; Pascale Fournier; Frédéric Menu; Maria P. Fernandez; Aude Herrera‐Belaroussi (Environmental Microbiology, 2015)
Summary Two major types of F rankia strains are usually recognized, based on the ability to sporulate in‐planta : spore‐positive ( Sp +) and spore‐negative ( Sp −). We carried out a study of Sp + and Sp − Frankia strains based on nodules collected on A lnus glutinosa , A lnus incana and A lnus viridis . The nodules were phenotyped using improved histology methods, and endophytic F rankia strain genotype was determined using a multilocus sequence analysis approach. An additional sampling was done to assess the relation between Sp + phenotype frequency and genetic diversity of Frankia strains at the alder stand scale. Our results revealed that (i) Sp + and Sp − Alnus ‐infective Frankia strains are genetically different even when sampled from the same alder stand and the same host–plant species; (ii) there are at least two distinct phylogenetic lineages of Sp + F rankia that cluster according to the host–plant species and without regard of geographic distance and (iii) genetic diversity of Sp + strains is very low at the alder stand scale compared with Sp − strains. Difference in evolutionary history and genetic diversity between Sp + and Sp − Frankia allows us to discuss the possible ecological role of in‐planta sporulation.

Genetic analysis and phenotypic characterization of leaf photosynthetic capacity in a sorghum (Sorghum spp.) diversity panel - Maria G. Salas Fernandez; Katie Strand; Martha T. Hamblin; Mark Westgate; Emily Heaton; Stephen Kresovich (Genetic Resources and Crop Evolution, 2015)

Metalloproteinase-9 contributes to inflammatory glia activation and nigro-striatal pathway degeneration in both mouse and monkey models of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinsonism - V. Annese; María-Trinidad Herrero; M. Di Pentima; A. Gomez; L. Lombardi; C. M. Ros; V. De Pablos; E. Fernandez-Villalba; Maria Egle De Stefano (Brain Structure and Function, 2015)

Association mapping of brassinosteroid candidate genes and plant architecture in a diverse panel of Sorghum bicolor - Maria B. Mantilla Perez; Jing Zhao; Yanhai Yin; Jieyun Hu; Maria G. Salas Fernandez (Theoretical and Applied Genetics, 2014)

Experimental study on the survival of the water hyacinth (Eichhornia crassipes (Mart.) Solms—Pontederiaceae) under different oil doses and times of exposure - Aline Lopes; Maria Teresa Fernandez Piedade (Environmental Science and Pollution Research, 2014)

Assessment of genetic diversity among sorghum landraces and their wild/weedy relatives in western Kenya using simple sequence repeat (SSR) markers - Maria G. Salas Fernandez; James A. Okeno; Evans Mutegi; Anania Fessehaie; Samantha Chalfant (Conservation Genetics, 2014)

Triple-layered mixed co-culture model of RPE cells with neuroretina for evaluating the neuroprotective effects of adipose-MSCs - David Rodriguez-Crespo; Salvatore Di Lauro; Amar K. Singh; Maria T. Garcia-Gutierrez; Manuel Garrosa; J. Carlos Pastor; Ivan Fernandez-Bueno; Girish K. Srivastava (Cell and Tissue Research, 2014)

Chromosome synapsis and recombination in simple and complex chromosomal heterozygotes of tuco-tuco (Ctenomys talarum: Rodentia: Ctenomyidae) - Ekaterina A. Basheva; Anna A. Torgasheva; Maria Jimena Gomez Fernandez; Emma Boston; Patricia Mirol; Pavel M. Borodin (Chromosome Research, 2014)

Allometric models for aboveground biomass estimation of the mangrove Avicennia schaueriana - Gustavo Calderucio Duque Estrada; Mário Luiz Gomes Soares; Daniel Medina Corrêa Santos; Viviane Fernandez; Paula Maria Moura de Almeida; Marciel Rocha de Medeiros Estevam; Maria Rita Olyntho Machado (Hydrobiologia, 2014)

Floristic variation across 600 km of inundation forests (Igapó) along the Negro River, Central Amazonia - Juan Carlos Montero; Maria Teresa Fernandez Piedade; Florian Wittmann (Hydrobiologia, 2014)

Screening of wild plants for use in the phytoremediation of mining-influenced soils containing arsenic in semiarid environments - Salvadora Martínez-López; Maria Jose Martínez-Sánchez; Carmen Pérez-Sirvent; Jaume Bech; Maria del Carmen Gómez Martínez; Antonio Juan García-Fernandez (Journal of Soils and Sediments, 2014)

Consistent plant residue removal causes decrease in minimum soil water content in a Mediterranean environment - Philip R. Ward; Margaret M. Roper; Ramona Jongepier; Maria M. Alonso Fernandez (Biologia, 2013)

Recommendations for a national agenda to substantially reduce cervical cancer - Jennifer S. Smith; Noel T. Brewer; Debbie Saslow; Kenneth Alexander; Mildred R. Chernofsky; Richard Crosby; Libby Derting; Leah Devlin; Charles J. Dunton; Jeffrey Engle; Maria Fernandez; Mona Fouad; et al. (Cancer Causes & Control, 2013)

A new haplotype of “Candidatus Liberibacter solanacearum” identified in the Mediterranean region - Warrick R. Nelson; Venkatesan G. Sengoda; Ana O. Alfaro-Fernandez; Maria I. Font; James M. Crosslin; Joseph E. Munyaneza (European Journal of Plant Pathology, 2013)

Antiseptic cyclodextrin-functionalized hydrogels and gauzes for loading and delivery of benzalkonium chloride - Maria José Garcia-Fernandez; Gilles Brackman; Tom Coenye; Angel Concheiro; Carmen Alvarez-Lorenzo (Biofouling, 2013)

IFNγ expression by an attenuated strain of Salmonella enterica serovar Typhimurium improves vaccine efficacy in susceptible TLR4-defective C3H/HeJ mice - Samia M. Al-Ojali; C. B. Tara Moore; Maria J. Fernandez-Cabezudo; Basel K. al-Ramadi (Medical Microbiology and Immunology, 2013)

A classification of major natural habitats of Amazonian white-water river floodplains (várzeas) - Wolfgang J. Junk; Maria Teresa Fernandez Piedade; Jochen Schöngart; Florian Wittmann (Wetlands Ecology and Management, 2012)

A Cannabigerol Quinone Alleviates Neuroinflammation in a Chronic Model of Multiple Sclerosis - Aitor G. Granja; Francisco Carrillo-Salinas; Alberto Pagani; María Gómez-Cañas; Roberto Negri; Carmen Navarrete; Miriam Mecha; Leyre Mestre; Bend L. Fiebich; Irene Cantarero; Marco A. Calzado; Maria L. Bellido; et al. (Journal of Neuroimmune Pharmacology, 2012)

8-Isoprostane, prostaglandin E2, C-reactive protein and serum amyloid A as markers of inflammation and oxidative stress in antiphospholipid syndrome: a pilot study - Savino Sciascia; Dario Roccatello; Maria Tiziana Bertero; Debora Di Simone; Domenico Cosseddu; Antonella Vaccarino; Mario Bazzan; Daniela Rossi; Cesar Garcia-Fernandez; Leticia Ceberio; Stefania Stella; Elisa Menegatti; et al. (Inflammation Research, 2012)

A short-term predictive system for surface currents from a rapidly deployed coastal HF radar network - Donald Barrick; Vicente Fernandez; Maria I. Ferrer; Chad Whelan; Øyvind Breivik (Ocean Dynamics, 2012)

Cellular and molecular analyses of coffee resistance to Hemileia vastatrix and nonhost resistance to Uromyces vignae in the resistance-donor genotype HDT832/2 - Inês Diniz; Pedro Talhinhas; Helena Gil Azinheira; Vítor Várzea; Clara Medeira; Isabel Maia; Anne-Sophie Petitot; Michel Nicole; Diana Fernandez; Maria do Céu Silva (European Journal of Plant Pathology, 2012)

Expression profiling of genes involved in the biotrophic colonisation of Coffea arabica leaves by Hemileia vastatrix - Ana Vieira; Pedro Talhinhas; Andreia Loureiro; Johannes Thürich; Sébastien Duplessis; Diana Fernandez; Maria do Céu Silva; Octávio S. Paulo; Helena Gil Azinheira (European Journal of Plant Pathology, 2012)

Diet and the risk of head and neck cancer: a pooled analysis in the INHANCE consortium - Shu-Chun Chuang; Mazda Jenab; Julia E. Heck; Cristina Bosetti; Renato Talamini; Keitaro Matsuo; Xavier Castellsague; Silvia Franceschi; Rolando Herrero; Deborah M. Winn; Carlo La Vecchia; Hal Morgenstern; et al. (Cancer Causes & Control, 2012)

Fluvastatin modulates renal water reabsorption in vivo through increased AQP2 availability at the apical plasma membrane of collecting duct cells - Giuseppe Procino; Claudia Barbieri; Monica Carmosino; Grazia Tamma; Serena Milano; Leonarda De Benedictis; Maria Grazia Mola; Yoskaly Lazo-Fernandez; Giovanna Valenti; Maria Svelto (Pflügers Archiv - European Journal of Physiology, 2011)

Lead, Zinc, Arsenic and Copper Pollution in the Alluvial Plain of a Mining Wadi: The Beal Case (Cartagena–La Union Mining District, SE Spain) - Oscar Gonzalez-Fernandez; Ignacio Queralt; Maria Luisa Carvalho; Gregorio Garcia (Water, Air, & Soil Pollution, 2011)

An examination of male and female odds ratios by BMI, cigarette smoking, and alcohol consumption for cancers of the oral cavity, pharynx, and larynx in pooled data from 15 case–control studies - Jay H. Lubin; Joshua Muscat; Mia M. Gaudet; Andrew F. Olshan; Maria Paula Curado; Luigino Dal Maso; Victor Wünsch-Filho; Erich M. Sturgis; Neonilia Szeszenia-Dabrowska; Xavier Castellsague; Zuo-Feng Zhang; Elaine Smith; et al. (Cancer Causes & Control, 2011)

A Classification of Major Naturally-Occurring Amazonian Lowland Wetlands - Wolfgang J. Junk; Maria Teresa Fernandez Piedade; Jochen Schöngart; Mario Cohn-Haft; J. Marion Adeney; Florian Wittmann (Wetlands, 2011)

Early Post-Natal Iron Administration Induces Astroglial Response in the Brain of Adult and Aged Rats - Liana Lisboa Fernandez; Maria Noêmia Martins de Lima; Felipe Scalco; Gustavo Vedana; Clívia Miwa; Arlete Hilbig; Mônica Vianna; Nadja Schröder (Neurotoxicity Research, 2011)

Detection of human-induced environmental disturbances in a show cave - Angel Fernandez-Cortes; Soledad Cuezva; Sergio Sanchez-Moral; Juan Carlos Cañaveras; Estefania Porca; Valme Jurado; Pedro Maria Martin-Sanchez; Cesareo Saiz-Jimenez (Environmental Science and Pollution Research, 2011)

Neonatal Iron Treatment Increases Apoptotic Markers in Hippocampal and Cortical Areas of Adult Rats - Clivia Pazin Miwa; Maria Noêmia Martins de Lima; Felipe Scalco; Gustavo Vedana; Raquel Mattos; Liana Lisboa Fernandez; Arlete Hilbig; Nadja Schröder; Monica R. M. Vianna (Neurotoxicity Research, 2011)

Erratum: Changes in Gene Expression Pattern of Human Primary Macrophages Induced by Carbosilane Dendrimer 2G-NN16 - Rafael Gras; Luis Almonacid; Paula Ortega; Maria J. Serramia; Rafael Gomez; F. Javier de la Mata; Luis A. Lopez-Fernandez; M. Angeles Muñoz-Fernandez (Pharmaceutical Research, 2011)

Novel silver-based nanoclay as an antimicrobial in polylactic acid food packaging coatings - Maria A. Busolo; Patricia Fernandez; Maria J. Ocio; Jose M. Lagaron (Food Additives & Contaminants: Part A, 2010)

Identification of coffee WRKY transcription factor genes and expression profiling in resistance responses to pathogens - Daniel Ramiro; Aida Jalloul; Anne-Sophie Petitot; Maria Fátima Grossi De Sá; Mirian P. Maluf; Diana Fernandez (Tree Genetics & Genomes, 2010)

Tissue-specific expression of olive S-adenosyl methionine decarboxylase and spermidine synthase genes and polyamine metabolism during flower opening and early fruit development - Maria C. Gomez-Jimenez; Miguel A. Paredes; Mercedes Gallardo; Nieves Fernandez-Garcia; Enrique Olmos; Isabel M. Sanchez-Calle (Planta, 2010)

Resistance to Meloidogyne incognita expresses a hypersensitive-like response in Coffea arabica - Erika Valéria Saliba Albuquerque; Regina Maria Dechechi Gomes Carneiro; Poliene Martins Costa; Ana Cristina Meneses Mendes Gomes; Marcilene Santos; Antonio Alves Pereira; Michel Nicole; Diana Fernandez; Maria Fatima Grossi-de-Sa (European Journal of Plant Pathology, 2010)

An α‐amylase is a novel receptor for Bacillus thuringiensis ssp. israelensis Cry4Ba and Cry11Aa toxins in the malaria vector mosquito Anopheles albimanus ( Diptera : Culicidae ) - Maria Teresa Fernandez‐Luna; Humberto Lanz‐Mendoza; Sarjeet S. Gill; Alejandra Bravo; Mario Soberon; Juan Miranda‐Rios (Environmental Microbiology, 2010)
Summary Bacillus thuringiensis ssp. israelensis ( Bti ) produces four Cry toxins (Cry4Aa, Cry4Ba, Cry10Aa and Cry11Aa), and two Cyt proteins (Cyt1Aa and Cyt2Ba), toxic to mosquito‐larvae of the genus Aedes , Anopheles and Culex , important human disease vectors that transmit dengue virus, malaria and filarial parasites respectively. Previous work showed that Bti is highly toxic to Anopheles albimanus , the main vector for transmission of malaria in Mexico. In this work, we analysed the toxicity of isolated Cry proteins of Bti and identified an An. albimanus midgut protein as a putative Cry4Ba and Cry11Aa receptor molecule. Biossays showed that Cry4Ba and Cry11Aa of Bti are toxic to An. albimanus larvae. Ligand blot assays indicated that a 70 kDa glycosylphosphatidylinositol‐anchored protein present in midgut brush border membrane vesicles of An. albimanus interacts with Cry4Ba and Cry11Aa toxins. This protein was identified as an α‐amylase by mass spectrometry and enzymatic activity assays. The cDNA that codes for the α‐amylase was cloned by means of 5′‐ and 3′‐RACE experiments. Recombinant α‐amylase expressed in Escherichia coli specifically binds Cry4Ba and Cry11Aa toxins.

Effects of crude oil on survival, morphology, and anatomy of two aquatic macrophytes from the Amazon floodplains - Aline Lopes; Sonia Maciel da Rosa-Osman; Maria Teresa Fernandez Piedade (Hydrobiologia, 2009)

Role of cannabis and endocannabinoids in the genesis of schizophrenia - Emilio Fernandez-Espejo; Maria-Paz Viveros; Luis Núñez; Bart A. Ellenbroek; Fernando Rodriguez de Fonseca (Psychopharmacology, 2009)

Effects of Community-Based Collaborative Group Characteristics on Social Capital - Cheryl L. Wagner; Maria E. Fernandez-Gimenez (Environmental Management, 2009)

Transgenic coffee fruits from Coffea arabica genetically modified by bombardment - Erika V. S. Albuquerque; Welcimar G. Cunha; Aulus E. A. D. Barbosa; Poliene M. Costa; João B. Teixeira; Giovanni R. Vianna; Glaucia B. Cabral; Diana Fernandez; Maria F. Grossi-de-Sa (In Vitro Cellular & Developmental Biology - Plant, 2009)

Intrinsically bent DNA sites in the Drosophila melanogaster third chromosome amplified domain - Fabrícia Gimenes; Mariana Aprígio Assis; Adriana Fiorini; Vânia Aparecida Mareze; Nadia Monesi; Maria Aparecida Fernandez (Molecular Genetics and Genomics, 2009)

Changes in Gene Expression Pattern of Human Primary Macrophages Induced by Carbosilane Dendrimer 2G-NN16 - Rafael Gras; Luis Almonacid; Paula Ortega; Maria J. Serramia; Rafael Gomez; F. Javier de la Mata; Luis A. Lopez-Fernandez; M. Angeles Muñoz-Fernandez (Pharmaceutical Research, 2009)

Binding Properties of Water-Soluble Carbosilane Dendrimers - Elzbieta Pedziwiatr; Dzmitry Shcharbin; Louis Chonco; Paula Ortega; F. Javier de la Mata; Rafael Gómez; Barbara Klajnert; Maria Bryszewska; Ma Angeles Muñoz-Fernandez (Journal of Fluorescence, 2009)

Wood growth of Tabebuia barbata (E. Mey.) Sandwith (Bignoniaceae) and Vatairea guianensis Aubl. (Fabaceae) in Central Amazonian black-water (igapó) and white-water (várzea) floodplain forests - Sinomar Ferreira da Fonseca Júnior; Maria Teresa Fernandez Piedade; Jochen Schöngart (Trees, 2009)

Effects of biosolarization as methyl bromide alternative for Meloidogyne incognita control on quality of soil under pepper - Margarita Ros; Carlos Garcia; Maria Teresa Hernandez; Alfredo Lacasa; Pedro Fernandez; Jose Antonio Pascual (Biology and Fertility of Soils, 2008)

Control of sulphide during anaerobic treatment of S-containing wastewaters by adding limited amounts of oxygen or nitrate - Dores G. Cirne; Frank P. van der Zee; Maria Fernandez-Polanco; Fernando Fernandez-Polanco (Reviews in Environmental Science and Bio/Technology, 2008)

Control of the flat-headed root borer Capnodis tenebrionis (Linné) (Coleoptera: Buprestidae) with the entomopathogenic nematode Steinernema carpocapsae (Weiser) (Nematoda: Steinernematidae) in a chitosan formulation in apricot orchards - Maria del Mar Martinez de Altube; Olaf Strauch; Gonzalo Fernandez De Castro; Alejandro Martinez Peña (BioControl, 2008)

Colorectal cancer screening among Latinos from U.S. cities along the Texas–Mexico border - Maria E. Fernandez; Rosario Wippold; Isabel Torres-Vigil; Theresa Byrd; Diamond Freeberg; Yadvindera Bains; Jessica Guajardo; Steven S. Coughlin; Sally W. Vernon (Cancer Causes & Control, 2008)

Multiple evidence for an early age pro-oxidant state in Down Syndrome patients - Federico V. Pallardó; Paolo Degan; Marco d’Ischia; Frank J. Kelly; Adriana Zatterale; Rita Calzone; Giuseppe Castello; Rafael Fernandez-Delgado; Christina Dunster; Ana Lloret; Paola Manini; Maria Antonietta Pisanti; et al. (Biogerontology, 2006)

DNA Bending in the Replication Zone of the C3 DNA Puff Amplicon of Rhynchosciara americana (Diptera: Sciaridae) - Adriana Fiorini; Fabiana Souza de Gouveia; Maria Albertina Miranda de Soares; Ann Jacob Stocker; Ricardo Rodrigues Ciferri; Maria Aparecida Fernandez (Molecular Biology Reports, 2006)

High-temperature single-crystal neutron diffraction study of natural chondrodite - Martin Kunz; George A. Lager; Hans-Beat Bürgi; Maria Teresa Fernandez-Diaz (Physics and Chemistry of Minerals, 2006)

Regulation of Contaminated Soils in Spain - A New Legal Instrument (4 pp) - Jose V. Tarazona; Maria D. Fernandez; M. Milagros Vega (Journal of Soils and Sediments, 2005)

Molecular characterization of the 5S ribosomal gene of the Bradysia hygida(Diptera:Sciaridae) - Lucinia De ftima chasko ribeiro; Maria Aparecida fernandez (Genetica, 2004)

Diversity of Frankia strains associated to Myrica gale in Western Europe: impact of host plant ( Myrica vs. Alnus ) and of edaphic factors - Valérie Huguet; Max Mergeay; Emilio Cervantes; Maria P. Fernandez (Environmental Microbiology, 2004)
Summary Myricaceae can be nodulated by a variety of Frankia strains isolated from other actinorhizal families. Consequently, the genus Myrica has been considered to have low specificity with respect to microsymbiont taxa. In contrast to controlled studies of Myrica infectious capacity, field studies in North America have indicated that M. gale symbionts belong to the genetic group of Alnus ‐infective strains. Myrica gale is the most widely distributed species in the genus so this study focused on describing the genetic diversity of M. gale ‐nodulating strains from 10 sites in Western Europe across a range of edaphic conditions. When possible, the specificity of M. gale ‐infective strains was compared with that of Alnus ‐infective strains from the same sites. Nodular strains from Belgium, France and Spain were characterized using PCR‐RFLP of rrs gene and 16S‐23S IGS. rrs ‐RFLP patterns showed a high level of homogeneity among European strains with one dominant genotype. IGS‐RFLP patterns revealed the largest inter and intrasite diversity in France. In Belgium, Frankia strains were found to occur in two groups according to soil pH and organic matter characteristics of the sites. European M. gale ‐infective strains were genetically different from European Alnus and North American M. gale ‐infective strains indicating the possibility of different pathways of co‐evolution among geographically isolated populations.

Factors controlling hydrochemical and trophic state variables in 86 shallow lakes in Europe - Peeter Nõges; Tiina Nõges; Lea Tuvikene; Halina Smal; Slawomir Ligeza; Ryszard Kornijów; Wojciech Peczula; Eloy Bécares; Francisco Garcia-Criado; Christina Alvarez-Carrera; Camino Fernandez-Alaez; Carmen Ferriol; et al. (Hydrobiologia, 2003)

Detection of QTL affecting fatty acid composition in the pig - Alex Clop; Cristina Ovilo; Miguel Perez-Enciso; Albert Cercos; Anna Tomas; Ana Fernandez; Agustina Coll; Josep M. Folch; Carmen Barragan; Isabel Diaz; Maria A. Oliver; Luis Varona; et al. (Mammalian Genome, 2003)

Observations on the Workshop as a Means of Improving Communication Between Holders of Traditional and Scientific Knowledge - HENRY P. HUNTINGTON; PATRICIA K. BROWN-SCHWALENBERG; KATHRYN J. FROST; MARIA E. FERNANDEZ-GIMENEZ; DAVID W. NORTON; DANIEL H. ROSENBERG (Environmental Management, 2002)

Testing Scandium Method to Quantify Suspended Particles Adhesion to the External Surface of Periphyton Communities - Umberto Sansone; Maria Belli; José A. Fernandez; Rob N. J. Comans; Zvonka Jeran; Fabio Cavolo; Sabrina Barbizzi; Paolo De Zorzi; Radojko Jacimovic (Water, Air, & Soil Pollution, 2002)

NOR Sites Detected by Ag-DAPI Staining of an Unusual Autosome Chromosome of Bradysia Hygida (Diptera:Sciaridae) Colocalize with C-banded Heterochromatic Region - Vanessa Pinatto Gaspar; Alex Rodrigues Borges; Maria Aparecida Fernandez (Genetica, 2002)

Vegetation change along gradients from water sources in three grazed Mongolian ecosystems - Maria Fernandez-Gimenez; Barbara Allen-Diaz (Plant Ecology, 2001)

Coffee consumption and bladder cancer in nonsmokers: a pooled analysis of case–control studies in European countries - Maria Sala; Sylvaine Cordier; Jenny Chang-Claude; Francesco Donato; Antonio Escolar-Pujolar; Francisco Fernandez; Carlos Alberto González; Eberhard Greiser; Karl-Heinz Jöckel; Elsebeth Lynge; Andrea`t Mannetje; Hermann Pohlabeln; et al. (Cancer Causes & Control, 2000)

Unequal X Chromosomes in Bradysia Hygida (Diptera:Sciaridae) Females: Karyotype Assembly and Morphometric Analysis - Alex Rodrigues Borges; Vanessa Pinatto Gaspar; Maria Aparecida Fernandez (Genetica, 2000)

The recombinant limb as a model for the study of limb patterning, and its application to muscle development - Marian Fernandez-Teran; M. Elisa Piedra; Maria A. Ros; J. F. Fallon (Cell and Tissue Research, 1999)

Transcription and weak expression of HLA-DRB6 : a gene with anomalies in exon 1 and other regions. - Victor M. Fernandez-Soria; Pablo Morales; Maria J. Castro; Belen Suarez; Maria J. Recio; Miguel A. Moreno; Estela Paz-Artal; A. Arnaiz-Villena (Immunogenetics, 1998)

Evidence that two genomic species of Rhizobium are associated with Medicago truncatula - Sophie Rome; Brigitte Brunel; Philippe Normand; Maria Fernandez; Jean-Claude Cleyet-Marel (Archives of Microbiology, 1996)